CN122000331A - Polycrystalline metal oxide with enriched grain boundaries - Google Patents

Polycrystalline metal oxide with enriched grain boundaries

Info

Publication number
CN122000331A
CN122000331A CN202610182632.7A CN202610182632A CN122000331A CN 122000331 A CN122000331 A CN 122000331A CN 202610182632 A CN202610182632 A CN 202610182632A CN 122000331 A CN122000331 A CN 122000331A
Authority
CN
China
Prior art keywords
composition
optionally
microcrystals
grain boundaries
particles
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
CN202610182632.7A
Other languages
Chinese (zh)
Inventor
A·普伦
D·奥弗
S·斯里拉穆鲁
K·沙辛
J·伦佩尔
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
CAMX Power LLC
Original Assignee
CAMX Power LLC
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Priority claimed from US16/250,622 external-priority patent/US10950857B2/en
Priority claimed from US16/250,615 external-priority patent/US10501335B1/en
Application filed by CAMX Power LLC filed Critical CAMX Power LLC
Publication of CN122000331A publication Critical patent/CN122000331A/en
Pending legal-status Critical Current

Links

Classifications

    • H—ELECTRICITY
    • H01—ELECTRIC ELEMENTS
    • H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
    • H01M4/00—Electrodes
    • H01M4/02—Electrodes composed of, or comprising, active material
    • H01M4/36—Selection of substances as active materials, active masses, active liquids
    • H01M4/48—Selection of substances as active materials, active masses, active liquids of inorganic oxides or hydroxides
    • H01M4/52—Selection of substances as active materials, active masses, active liquids of inorganic oxides or hydroxides of nickel, cobalt or iron
    • H01M4/525—Selection of substances as active materials, active masses, active liquids of inorganic oxides or hydroxides of nickel, cobalt or iron of mixed oxides or hydroxides containing iron, cobalt or nickel for inserting or intercalating light metals, e.g. LiNiO2, LiCoO2 or LiCoOxFy
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01G—COMPOUNDS CONTAINING METALS NOT COVERED BY SUBCLASSES C01D OR C01F
    • C01G53/00—Compounds of nickel
    • C01G53/40—Complex oxides containing nickel and at least one other metal element
    • C01G53/42—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01G—COMPOUNDS CONTAINING METALS NOT COVERED BY SUBCLASSES C01D OR C01F
    • C01G53/00—Compounds of nickel
    • C01G53/40—Complex oxides containing nickel and at least one other metal element
    • C01G53/42—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2
    • C01G53/44—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese
    • C01G53/50—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2
    • C01G53/502—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2 containing lithium and cobalt
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01G—COMPOUNDS CONTAINING METALS NOT COVERED BY SUBCLASSES C01D OR C01F
    • C01G53/00—Compounds of nickel
    • C01G53/40—Complex oxides containing nickel and at least one other metal element
    • C01G53/42—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2
    • C01G53/44—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese
    • C01G53/50—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2
    • C01G53/502—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2 containing lithium and cobalt
    • C01G53/504—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2 containing lithium and cobalt with the molar ratio of nickel with respect to all the metals other than alkali metals higher than or equal to 0.5, e.g. Li(MzNixCoyMn1-x-y-z)O2 with x ≥ 0.5
    • C01G53/506—Complex oxides containing nickel and at least one other metal element containing alkali metals, e.g. LiNiO2 containing manganese of the type (MnO2)n-, e.g. Li(NixMn1-x)O2 or Li(MyNixMn1-x-y)O2 containing lithium and cobalt with the molar ratio of nickel with respect to all the metals other than alkali metals higher than or equal to 0.5, e.g. Li(MzNixCoyMn1-x-y-z)O2 with x ≥ 0.5 with the molar ratio of nickel with respect to all the metals other than alkali metals higher than or equal to 0.8, e.g. Li(MzNixCoyMn1-x-y-z)O2 with x ≥ 0.8
    • H—ELECTRICITY
    • H01—ELECTRIC ELEMENTS
    • H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
    • H01M10/00—Secondary cells; Manufacture thereof
    • H01M10/05—Accumulators with non-aqueous electrolyte
    • H01M10/052—Li-accumulators
    • H—ELECTRICITY
    • H01—ELECTRIC ELEMENTS
    • H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
    • H01M4/00—Electrodes
    • H01M4/02—Electrodes composed of, or comprising, active material
    • H01M4/36—Selection of substances as active materials, active masses, active liquids
    • H01M4/362—Composites
    • H01M4/366—Composites as layered products
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2002/00—Crystal-structural characteristics
    • C01P2002/50—Solid solutions
    • C01P2002/52—Solid solutions containing elements as dopants
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2002/00—Crystal-structural characteristics
    • C01P2002/70—Crystal-structural characteristics defined by measured X-ray, neutron or electron diffraction data
    • C01P2002/77—Crystal-structural characteristics defined by measured X-ray, neutron or electron diffraction data by unit-cell parameters, atom positions or structure diagrams
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2002/00—Crystal-structural characteristics
    • C01P2002/80—Crystal-structural characteristics defined by measured data other than those specified in group C01P2002/70
    • C01P2002/85—Crystal-structural characteristics defined by measured data other than those specified in group C01P2002/70 by XPS, EDX or EDAX data
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2004/00—Particle morphology
    • C01P2004/01—Particle morphology depicted by an image
    • C01P2004/03—Particle morphology depicted by an image obtained by SEM
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2004/00—Particle morphology
    • C01P2004/01—Particle morphology depicted by an image
    • C01P2004/04—Particle morphology depicted by an image obtained by TEM, STEM, STM or AFM
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2004/00—Particle morphology
    • C01P2004/50—Agglomerated particles
    • C—CHEMISTRY; METALLURGY
    • C01—INORGANIC CHEMISTRY
    • C01P—INDEXING SCHEME RELATING TO STRUCTURAL AND PHYSICAL ASPECTS OF SOLID INORGANIC COMPOUNDS
    • C01P2006/00—Physical properties of inorganic compounds
    • C01P2006/40—Electric properties
    • H—ELECTRICITY
    • H01—ELECTRIC ELEMENTS
    • H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
    • H01M4/00—Electrodes
    • H01M4/02—Electrodes composed of, or comprising, active material
    • H01M2004/026—Electrodes composed of, or comprising, active material characterised by the polarity
    • H01M2004/028—Positive electrodes
    • Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
    • Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
    • Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
    • Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
    • Y02E60/10—Energy storage using batteries

Landscapes

  • Chemical & Material Sciences (AREA)
  • Organic Chemistry (AREA)
  • Inorganic Chemistry (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Electrochemistry (AREA)
  • General Chemical & Material Sciences (AREA)
  • Composite Materials (AREA)
  • Engineering & Computer Science (AREA)
  • Manufacturing & Machinery (AREA)
  • Battery Electrode And Active Subsutance (AREA)
  • Inorganic Compounds Of Heavy Metals (AREA)
  • Secondary Cells (AREA)

Abstract

Electrochemically active secondary particles are provided that provide excellent capacity and improved cycle life. The particles are characterized by selectively enriched grain boundaries, wherein the grain boundaries are enriched in Al. Al enrichment reduces the impedance increase during cycling, thereby improving capacity and cycle life. Methods of forming the electrochemically active material are also provided, as are electrodes and electrochemical cells using the secondary particles.

Description

Polycrystalline metal oxide with enriched grain boundaries
The application is a divisional application of patent application No. 201980094065.8, the application date of the original application is 2019, 10 month and 23 days, and the application is named as 'polycrystalline metal oxide with enriched grain boundaries'.
Cross reference to related applications
The present application depends on and claims priority from U.S. patent application Ser. No. 16/250,615 filed on 1 month 17 of 2019, U.S. patent application Ser. No. 16/250,762 filed on 1 month 17 of 2019, and U.S. patent application Ser. No. 16/250,622 filed on 1 month 17 of 2019, each of which is incorporated herein by reference in its entirety.
FIELD
Polycrystalline metal oxide particles, methods of making the same, and electrochemical cells or batteries (batteries) containing the same are disclosed.
Background
Layered lithium nickel oxide (LiNiO 2) based materials have been developed for lithium ion battery cathodes because they generally have lower cost, higher capacity and higher rate capability than the LiCoO 2 cathode materials that have been dominant in the past. But pure LiNiO 2 materials exhibit poor electrochemical stability and cycling performance. To address this, non-nickel elemental additives have been formulated into LiNiO 2 that stabilize the structure to improve cycling performance, but generally at the expense of discharge capacity. As the demand for energy density increases, research has focused on optimizing and reducing these non-nickel additives to harvest the capacity of high Ni materials while maintaining cycle performance.
Accordingly, new materials are needed that address the need for high capacity materials with long cycle life. The materials and methods of forming these materials provided herein address this need by maintaining high capacity over long cycle life.
SUMMARY
The following summary is provided to facilitate an understanding of some of the innovative features unique to the present disclosure and is not intended to be a full description. A full appreciation of the various aspects of the disclosure can be gained by taking the entire specification, claims, drawings, and abstract as a whole.
Secondary particles are provided that are found to have greatly reduced impedance growth when used as cathode electrochemically active materials in lithium ion secondary batteries (Li-ion secondary cell). It was found that by selectively enriching the grain boundaries between crystallites in the secondary particles with a combination of Co and Al, improved impedance properties can be achieved and these improved impedance properties are achieved in many electrochemically active materials of different compositions.
Thus provided are particles comprising a plurality of crystallites comprising a first composition comprising lithium, nickel and oxygen, between adjacent crystallites of the plurality of crystallites and comprising a layer having a layer shapeA grain boundary of the second composition of NaFeO 2 -type structure, cubic structure, spinel structure, or a combination thereof, wherein the concentration of aluminum in the grain boundary is greater than the concentration of aluminum in the crystallites, and wherein the concentration of cobalt in the grain boundary is greater than the concentration of cobalt in the crystallites. In some aspects, it was found that Al enrichment of grain boundaries was not uniform, complete, or achieved, but that Al grain boundary enrichment, optionally Co and Al grain boundary enrichment, could be achieved when using the manufacturing methods provided herein. Thus, in some aspects, al is substantially uniformly distributed among the plurality of particles.
In some aspects, the amount of Al in the grain boundaries is 0.01 at% to 10 at% of the total transition metal amount in the remainder of the secondary particles. Optionally, the amount of Co in the grain boundaries is 0 at% to 10 at% of the total transition metal amount in the remainder of the secondary particles, optionally 0.1 at% to 10 at% of the total transition metal amount in the remainder of the secondary particles. Optionally, the amount of Al in the grain boundaries is 0.01 at% to 5 at% of the total transition metal amount in the remainder of the secondary particles and the amount of Co in the grain boundaries is 0.01 at% to 10 at% of the total transition metal amount in the remainder of the secondary particles. Optionally, the amount of aluminum in the grain boundaries is equal to or less than the amount of Co in the grain boundaries.
In some aspects, the plurality of crystallites has an alpha-NaFeO 2 layered structure, a cubic structure, a spinel structure, or a combination thereof.
Optionally, the first composition, the second composition, or both of any of the above aspects or other aspects are defined by Li 1+ xMO2+y, wherein
-0.1≤x≤0.3,
-0.3.Ltoreq.y≤0.3 and
Wherein M comprises greater than or equal to 10 atomic percent nickel. Optionally, M comprises greater than or equal to 75 at atomic% of nickel. Optionally, the entire grain boundary comprises cobalt in an amount of about 2 at% to about 99 at% and aluminum in an amount of about 2 at% to about 99 at%. Optionally, in the first composition, the second composition, or both, M further comprises an additional metal, wherein the additional metal is present in an amount of about 1 at% to about 90 at%, the additional metal is selected from Mg, sr, co, al, ca, cu, zn, mn, V, ba, zr, ti, nb, ta, cr, fe, mo, W, hf, B and any combination thereof, whereby the one or more additional elements are optionally located in the Li layer, the M layer, or both.
Optionally, the crystallites comprise cobalt, having a cobalt concentration in the range of 1 at% to about 50 at%, optionally in the range of 1 at% to about 15 at%. In some aspects, the crystallites comprise Mn present in an amount of about 1 at% to about 60 at%, and the grain boundaries comprise Mn present in an amount of about 1 at% to about 60 at%. In other aspects, the grain boundaries comprise Ni, co, and Al. Optionally, the Ni concentration in the grain boundaries is greater than 75 at%.
Some aspects of the particles include an overcoat layer on the surface of the particles, the overcoat layer comprising an oxide of one or more elements selected from Al, zr, Y, co, ni, mg and Li, a fluoride comprising one or more elements selected from Al, zr, and Li, a carbonate comprising one or more elements selected from Al, co, ni, mn and Li, or a phosphate or sulfate comprising one or more elements selected from Al and Li.
In other aspects provided herein, an electrochemically active polycrystalline secondary particle is provided comprising a plurality of crystallites comprising a first composition defined by Li 1+xMO2+y, wherein-0.1 +.0.3, -0.3 +.0.3, and wherein M comprises greater than or equal to 80 atomic percent nickel, and a grain boundary between adjacent crystallites of the plurality of crystallites and comprising a second composition, the second composition optionally defined by Li 1+ xMO2+y wherein-0.1 +.0.3, -0.3 +.y +.0.3, and optionally having an alpha-NaFeO 2 type layered structure, a cubic structure, or a combination thereof, wherein the concentration of aluminum in the grain boundary is greater than the concentration of aluminum in the crystallites, and optionally wherein the concentration of cobalt in the grain boundary is greater than the concentration of cobalt in the crystallites, and wherein the aluminum is substantially uniformly distributed in the grain boundary. Optionally, the concentration of cobalt in the crystallites is from about 0 to about 17 atomic percent of M in the first composition, and the amount of cobalt in the grain boundaries is from about 0 to about 10 atomic percent of M in the crystallites. Optionally, M further comprises one or more elements selected from Na, K, al, mg, co, mn, ca, sr, ba, zn, ti, zr, Y, cr, mo, fe, V, si, ga and B, which are located in the Li layer, M layer, or both of the crystallites. Optionally, M comprises greater than or equal to 90 atomic% of nickel.
Electrochemical cells are also provided. The electrochemical cell includes a cathode active material. The cathode active material optionally includes any of the particles provided above or elsewhere herein. The electrochemical cell is optionally characterized by an impedance increase of less than 100% for greater than 100 cycles at 45 ℃, optionally less than 100% for greater than 200 cycles at 45 ℃.
There is also provided an electrochemical cell, optionally a secondary cell, optionally a lithium ion secondary cell, comprising an anode, an electrolyte, and a cathode comprising an electrochemically active cathode active material comprising a plurality of particles comprising a plurality of crystallites each comprising a first composition comprising lithium, nickel, and oxygen, between adjacent crystallites of the plurality of crystallites and comprising a layer having a layer shape-A grain boundary of a second composition of NaFeO 2 -type structure, cubic structure, spinel structure, or a combination thereof, wherein the electrochemically active cathode active material has an initial discharge capacity of 180 mAh/g or greater, and wherein the electrochemical cell has an impedance growth at 4.2V of less than 50% for greater than 100 cycles at 45 ℃. The electrochemical cell is optionally characterized by an impedance increase at 50% charge of less than 50% for greater than 200 cycles at 45 ℃, optionally less than 120% for greater than 200 cycles at 45 ℃. In some aspects, the electrochemical cell is characterized by an impedance increase at 50% charge state of less than 50% for greater than 200 cycles at 45 ℃. Optionally, each crystallite comprises lithium, nickel, cobalt and oxygen. Optionally, the crystallites comprise Al, mn, mg, or a combination thereof.
Optionally, the first composition, the second composition, or both of any of the above aspects or other aspects are defined by Li 1+ xMO2+y, wherein
-0.95≤x≤0.3,
-0.3.Ltoreq.y≤0.3 and
Wherein M comprises greater than or equal to 80 atomic percent nickel. Optionally, M in the first composition comprises greater than or equal to 75 atomic percent of nickel relative to the total transition metals in the first composition. In the second composition, M is optionally less than or equal to 90 at% relative to the total transition metals in the second composition. Optionally, the entire grain boundary comprises cobalt in an amount of about 2 at% to about 99 at% and aluminum in an amount of about 2 at% to about 99 at%. Optionally, in the first composition, the second composition, or both, M further comprises an additional metal, wherein the additional metal is present in an amount of about 1 at% to about 90 at% relative to the total metal in the respective first or second composition, the additional metal is selected from Mg, sr, co, al, ca, cu, zn, mn, V, ba, zr, ti, nb, ta, cr, fe, mo, W, hf, B and any combination thereof, whereby the one or more additional elements are optionally located in the Li layer, the M layer, or both.
Optionally, the crystallites comprise cobalt, having a cobalt concentration in the range of 1 at% to about 50 at%, optionally in the range of 1 at% to about 15 at%, relative to the total transition metal in the first composition. In some aspects, the crystallites comprise Mn present in an amount of about 1 at% to about 60 at%, and the grain boundaries comprise Mn present in an amount of about 1 at% to about 60 at%. In other aspects, the grain boundaries comprise Ni, co, and Al. Optionally, the Ni concentration in the grain boundaries is greater than 75 at%.
Brief Description of Drawings
The aspects set forth in the drawings are illustrative and exemplary and are not intended to limit the subject matter defined by the claims. The following detailed description of exemplary aspects may be understood when read in conjunction with the following drawings, and wherein:
FIG. 1 is a schematic perspective view of a cross-section of a secondary particle provided in accordance with aspects described herein;
FIG. 2 illustrates capacity fade for a full cell (full cell) using secondary particles according to some aspects provided herein;
FIG. 3 illustrates an impedance increase for a full cell using secondary particles according to some aspects provided herein;
FIG. 4 illustrates an EDS map (EDS MAPPING) of the secondary particles provided herein, with grain boundaries enriched in Al alone or in the presence of Co;
FIG. 5 illustrates a Scanning Transmission Electron Microscopy (STEM) image of a small slice of secondary particles from and made by enriching the grain boundaries with 1.9 at% Al and 4 at% Co, and showing the locations where 3 EDS point analyses were performed, according to one aspect provided herein, containing several crystallites;
FIG. 6 illustrates the EDS spectra of the three points shown in FIG. 5;
FIG. 7 illustrates STEM images of a small slice of secondary particles from and made by enriching the grain boundaries with 1.9 at% Al in the absence of Co in the process solution and showing the locations where 2 EDS point analyses were performed, according to one aspect provided herein, containing several crystallites;
FIG. 8 illustrates the EDS spectra of the three points shown in FIG. 7;
FIG. 9 illustrates an EDS map of secondary particles provided herein, made by non-aqueous processing using Al alone or in the presence of Co in a process solution during manufacturing to enrich the grain boundaries of the primary particles;
FIG. 10 illustrates the cyclic capacity fade and their dependence on additional Co content for a cell formed with a cathode comprising 0 at% Al in a process solution and 0.5 at% Al in a process solution of an active material enriched in grain boundaries according to one aspect provided herein;
FIG. 11 illustrates the increase in resistance and their dependence on additional Co content of cells formed with cathodes comprising 0 at% Al in the process solution and 0.5 at% Al in the process solution prepared according to one aspect of grain boundary enriched active materials provided herein;
FIG. 12 illustrates the synergistic benefits observed by including Al in addition to Co enrichment in the grain boundaries;
FIG. 13 illustrates cyclic capacity fade and impedance growth for a battery having a grain boundary enriched cathode material with grain boundary enrichment by a3 at% Co process application (process application) with different Al content, in accordance with some aspects provided herein;
FIG. 14 illustrates the increase in resistance of cathode active materials provided herein according to aspects at various Al/Co enrichment atomic% ratios;
FIG. 15 illustrates STEM and EDS analysis results for 3 points in a small slice of secondary particles of NCA prepared herein, as Al-enriched grain boundaries in the presence of Co;
Figure 16 illustrates the cyclic capacity fade of a cell formed with a cathode comprising a control or a NCA active material enriched in grain boundaries according to one aspect provided herein;
figure 17 illustrates the increase in impedance of a cell formed with a cathode comprising a control or a NCA active material enriched in grain boundaries according to one aspect provided herein;
FIG. 18 illustrates the cyclic capacity fade for a cell formed with a cathode comprising a control or a grain boundary enriched NCM active material according to one aspect provided herein, and
Figure 19 illustrates the increase in resistance of a cell formed with a cathode comprising a control or a NCM active material enriched in grain boundaries according to one aspect provided herein.
Detailed description of the preferred embodiments
The following description of certain aspects is merely exemplary in nature and is in no way intended to limit the scope of the disclosure, its application, or uses, these aspects of course being variable. Materials and methods are described in connection with non-limiting definitions and terms included herein. These definitions and terms are not intended to limit the scope or practice of the present disclosure, but are used for exemplary and descriptive purposes only. Although the method or composition is described as a sequence of individual steps or using specific materials, it is to be understood that the steps or materials may be interchanged such that the description of the invention may include multiple parts or steps arranged in many ways as will be readily appreciated by those of skill in the art.
It will be understood that, although the terms "first," "second," "third," etc. may be used herein to describe various elements, components, regions, layers and/or sections, these elements, components, regions, layers and/or sections should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or section from another element, component, region, layer or section. Thus, unless specified otherwise, a "first element," "component," "region," "layer" or "section" discussed below could be termed a second (or other) element, component, region, layer, or section without departing from the teachings herein.
The terminology used herein is for the purpose of describing particular aspects only and is not intended to be limiting. As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms as well, including "at least one," unless the context clearly indicates otherwise. "or" means "and/or". The term "and/or" as used herein includes any and all combinations of one or more of the associated listed items. It will be further understood that the terms "comprises" and/or "comprising," when used in this specification, specify the presence of stated features, regions, integers, steps, operations, elements, and/or components, but do not preclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and/or groups thereof. The term "or a combination thereof" refers to a combination comprising at least one of the foregoing elements.
Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning that is consistent with their meaning in the context of the relevant art and the present disclosure and will not be interpreted in an idealized or overly formal sense unless expressly so defined herein.
The LiMO 2 type of Ni-based layered material is a dense polycrystalline agglomerate of primary crystals (PRIMARY CRYSTAL). These are typically manufactured from various precursor materials using standard solid state methods at temperatures of 600 ℃ to 900 ℃. The precursor material is typically a transition metal hydroxide (M (OH) 2), a lithium precursor (e.g., liOH or Li 2CO3), or an inorganic precursor of other dopants (e.g., hydroxide, carbonate, nitrate). During heating of the precursor mixture, polycrystalline LiMO 2 is formed with the discharge of a gas such as H 2O、CO2 or NO 2.
The result of sintering under the correct conditions and using a suitable precursor is the formation of a number of primary crystallites, which are shaped into larger secondary particles that can act as electrochemically active material. It has been previously found that the region between these primary crystallites, i.e., the grain boundaries, can be selectively enriched for Co (as found in U.S. Pat. No. 9,209,455). In the present disclosure, the inventors have found that by substituting Al for some of the enriched Co in the grain boundaries, significant further improvements can be achieved, further reducing the impedance growth and improving the cycle life. It is understood that the synergistic relationship between Co and Al in the grain boundaries, particularly at Co levels of 2 mole% Co to 5 mole% Co (relative to the total M content in the crystallites) combined with lower relative Al levels, significantly reduces the impedance growth and improves the cycle life of electrochemical cells using the material as cathode active material.
Accordingly, the present disclosure provides improved electrochemically active materials, such as those suitable for use in the positive electrode (cathode) of Li-ion secondary batteries, that reduce the rate of impedance increase and/or the rate of capacity fade during the charge/discharge cycles of the battery relative to existing materials. Various methods are also provided for achieving high discharge capacity cathode active materials that exhibit a reduction in resistance increase and a reduction in capacity fade upon their cycling as compared to the same material in the absence of Co and Al enrichment in the grain boundaries.
The polycrystalline layered structured lithiated metal oxides provided herein exhibit enhanced electrochemical performance and stability. The composition prevents performance degradation of electrochemically cycled Ni-containing polycrystalline LiMO 2 -based materials while maintaining other desirable end-use article properties, such as electrochemical capacity of rechargeable lithium ion cathodes made from such layered metal oxides, by reducing the rate of impedance increase during electrochemical cycling. Such Co and Al grain boundary enriched materials can be readily manufactured by calcining a green formulation (green body formulation) comprising LiOH and a precursor hydroxide or carbonate to form particles having a sharp grain boundary (DEFINED GRAIN boundaries), and then enriching the grain boundary with a combination of Co and Al such that the resulting particles have grain boundaries in which the Co and Al concentrations in the grain boundaries are greater than before enrichment and optionally greater than the concentration within the primary crystallites, the outer surfaces of the primary crystallites defining the edges of the grain boundaries in the secondary particles.
Thus, compositions, systems and methods of manufacturing and using polycrystalline layered structured lithiated metal oxides having Co and Al-enriched grain boundaries in lithium ion secondary batteries as a means to achieve high initial discharge capacity and low resistance increase during cycling are provided, thereby overcoming previous challenges in high nickel formulations that may also have high discharge capacity (e.g., >205 mAh/g at C/20).
The provided material includes particles comprising a plurality of crystallites, each crystallite comprising a first composition. Particles formed from a plurality of crystallites may be referred to as secondary particles. The particles provided herein are uniquely tailored to have grain boundaries between primary crystallites. After they are formed, these grain boundaries are enriched with a combination of Co and Al, optionally at specific relative concentrations of Co and Al, to produce particles that provide reduced impedance growth during cycling to improve the performance and cycle life of a battery comprising the particles as the cathode component.
The particles are believed to include grain boundaries formed from or including the second composition, wherein the concentration of, for example, cobalt and aluminum in the grain boundaries is greater than the concentration of, for example, cobalt and aluminum in the primary crystallites adjacent thereto. The concentration of Co and Al in the grain boundaries is optionally on average greater than the average Co and Al concentration within adjacent crystallites. The materials provided herein optionally have relatively uniform Co and/or Al concentrations (if any) within the crystallites. Whether uniform or not, the concentration of Co and Al in the grain boundaries is greater than the average Co and Al concentrations (individually or in combination) within adjacent crystallites. Optionally, the provided material includes an additional overcoat layer that may be disposed on the outer surface of the secondary particles to provide coated secondary particles.
In some aspects of the particles provided herein, the first composition comprises a polycrystalline layered structure lithiated metal oxide defined by the composition Li 1+xMO2+y, and optionally a battery or battery formed therefrom, wherein-0.1 +.0.3 and-0.3 +≤y +.0.3. In some aspects, x is-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.30. In some aspects, y is-0.3, optionally-0.2, optionally-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is greater than or equal to -0.30、-0.29、-0.28、-0.27、-0.26、-0.25、-0.24、-0.23、-0.22、-0.21、-0.20、-0.19、-0.18、-0.17、-0.16、-0.15、-0.14、-0.13、-0.12、-0.11、-0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.3.
It is to be appreciated that in some aspects, li need not be entirely Li, but may be partially substituted with one or more elements selected from Mg, sr, na, K and Ca. The one or more elements that replace Li are optionally present at 10 atomic% or less, optionally 5 atomic% or less, optionally 3 atomic% or less, optionally no greater than 2 atomic%, wherein the% is relative to the total Li in the material.
M provided in the first composition includes Ni. The Ni amount in the first composition is optionally 10 atomic% to 100 atomic% (at%) of the total M. Optionally, the Ni component of M is greater than or equal to 75 at%. Optionally, the Ni component of M is 80 at% or greater. Optionally, the Ni component of M is greater than or equal to 85 at% optionally, the Ni component of M is greater than or equal to 90 at%. Optionally, the Ni component of M is greater than or equal to 95 at%. Optionally, the Ni component of M is 75 at%、76 at%、77 at%、78 at%、79 at%、80 at%、81 at%、82 at%、83 at%、84 at%、85 at%、86 at%、87 at%、88 at%、89 at%、90 at%、91 at%、92 at%、93 at%、94 at%、95 at%、96 at%、97 at%、98 at%、99 at%、99.5 at%、99.9 at% or greater than or equal to 100 at%.
In some aspects, M in the first composition is Ni alone or in combination with one or more additional elements. The additional element is optionally a metal. Optionally, the additional elements may include either Al, mg, co, mn, ca, sr, zn, ti, Y, cr, mo, fe, V, si, ga or one or more of B. In particular aspects, the additional elements may include Mg, co, al, or a combination thereof. Optionally, the additional element may be Mg, al, V, ti, B or Mn or a combination thereof. Optionally, the additional element is selected from Mg, al, V, ti, B or Mn. Optionally, the additional element is selected from Mg, co and Al. Optionally, the additional element is selected from Ca, co and Al. In some aspects, the additional element is Mn or Mg, or Mn and Mg. Optionally, the additional element is Mn, co, al, or any combination thereof. Optionally, the additional elements include Co and Mn. Optionally, the additional elements are Co and Al. Optionally, the additional element is Co.
The additional elements of the first composition may be present in an amount of from about 1 to about 90 at%, particularly from about 5 to about 80 at%, more particularly from about 10 to about 70 at%, of M in the first composition. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, particularly about 2 to about 18 at%, more particularly about 4 to about 16 at%, of M in the first composition. In some illustrative examples, M is about 75-100 at% Ni, 0-15 at% Co, 0-15 at% Mn, and 0-10 at% additional elements.
Within the polycrystalline material, the crystallites may have any suitable shape, which may be the same or different within the particles. Furthermore, the shape of each crystallite may be the same or different in different particles. Due to its crystalline nature, the crystallites may be faceted (be faceted), the crystallites may have many planar surfaces and the shape of the crystallites may approximate a geometric shape. In some aspects, crystallites may be sintered (fused) to adjacent crystallites having mismatched crystal planes (MISMATCHED CRYSTAL PLANE). The crystallites may optionally be polyhedra. The crystallites may have a rectilinear shape and a part or the whole of the crystallites may be rectilinear when viewed in cross section. The crystallites may be square, hexagonal, rectangular, triangular or a combination thereof.
In a particular aspect, the secondary particles have Co and Al enriched grain boundaries, optionally wherein the atomic percent of Co and Al in the grain boundaries is higher than the atomic percent of Co and Al in the ensemble averaged crystallites. Referring to fig. 1 as an exemplary illustration, grain boundaries 20, 21 are between adjacent crystallites 10 and comprise a second composition. The second composition may be described in accordance with U.S. patent nos. 9,391,317 and 9,209,455, except that both Co and Al must be independently enriched in the grain boundaries relative to their respective concentrations in the crystallites, and in some aspects, since the concentrations of Co and Al are within a certain concentration range, a synergistic effect may be provided in terms of reducing impedance or improving cycle life. The second composition optionally has a layered alpha-NaFeO 2 type structure, a cubic structure, or a combination thereof. As described above, the concentration of Co and Al in the grain boundaries may be greater than the concentration of Co and Al in the crystallites. Particular mention is made of aspects in which the grain boundaries have a lamellar α -NaFeO 2 type structure. Mention is made in particular of another aspect in which the grain boundaries have a structure of the alpha-NaFeO 2 type containing defects. Mention is made in particular of another aspect in which a part of the grain boundaries have a cubic structure or a spinel structure.
The second composition, which is partially or fully present in the grain boundaries, optionally includes lithiated metal oxides defined by the composition Li 1+xMO2+y, wherein-0.1≤x≤0.3 and-0.3≤y≤0.3. Optionally, the second composition is the same as the first composition except that Co and Al are present in the second composition, or the concentration of Co and Al is increased relative to the first composition. In some aspects of the second composition, x is-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.30. In some aspects, y is-0.3, optionally-0.2, optionally-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is greater than or equal to -0.30、-0.29、-0.28、-0.27、-0.26、-0.25、-0.24、-0.23、-0.22、-0.21、-0.20、-0.19、-0.18、-0.17、-0.16、-0.15、-0.14、-0.13、-0.12、-0.11、-0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.3.
M provided in the second composition includes Co and Al. The Ni amount, if present, is optionally 0.01 atomic% to 99 atomic% (at%) of M. Optionally, M in the second composition is free of Ni. Optionally, the amount of Ni in the second composition (i.e., relative concentration) is lower than the amount of Ni in the first composition in relative atomic% (relative to the respective composition in which Ni is present). Optionally, the Ni component of M is less than or equal to 1 at%. Optionally, the Ni component of M is less than or equal to 5 at%. Optionally, the Ni component of M is less than or equal to 10 at%. Optionally, the Ni component of M is less than or equal to 20 at%. Optionally, the Ni component of M is less than or equal to 75 at%. Optionally, the Ni component of M is 80 at% or less. Optionally, the Ni component of M is less than or equal to 85 at%. Optionally, the Ni component of M is less than or equal to 90 at%. Optionally, the Ni component of M is less than or equal to 95 at%. Optionally, the Ni component of M is 75 at%、76 at%、77 at%、78 at%、79 at%、80 at%、81 at%、82 at%、83 at%、84 at%、85 at%、86 at%、87 at%、88 at%、89 at%、90 at%、91 at%、92 at%、93 at%、94 at%、95 at%、96 at%、97 at%、98 at%、99 at% or less or 99.9. 99.9 at%.
For the materials optionally provided herein, the nominal or overall formulated composition of the secondary particles (e.g., characterized by Inductively Coupled Plasma (ICP)), optionally the first composition or optionally the second composition, is defined by the formula LiMO, wherein M is Ni and optionally one or more additional metals, at least Co and Al must be included in the second composition. The mole fraction of Co and Al in the first composition defining the microcrystalline composition, if present, is lower than the mole fraction of total Co and Al (individually or in combination) in the total particle composition as determined by ICP. The mole fraction of Co and Al (individually or in combination) in the first composition may be 0. The mole fraction of Co and Al (individually or in combination) in the second composition that defines the grain boundaries is higher than the mole fraction of Co and Al (individually or in combination) in the total particles as determined by ICP.
The second composition located within the grain boundaries comprises Co and Al, optionally provided that the concentration of Co and Al (individually or in combination) in the grain boundaries is greater than the concentration of Co and Al (individually or in combination) in the crystallites, optionally wherein the concentration of Co in the grain boundaries is greater than the concentration of Co in the crystallites, and optionally wherein the concentration of Al in the grain boundaries is greater than the concentration of Al in the crystallites. It was found that using a method capable of enriching Co and Al in the grain boundaries, a liquid solution comprising an amount of Co equal to or between 0 at% and 8 at%, optionally equal to or between 3 at% and 5 at% Co relative to the total transition metal of the first composition to be enriched can be supplemented with 0.01 at% to 10 at% Al, optionally 1.5 at% or less Al, and form a material that exhibits a significantly reduced impedance increase during cycling, wherein the added Co and Al are incorporated into the grain boundaries of the secondary particles.
The volume fraction of grain boundaries within a given secondary particle will vary because the primary particle size distribution varies with overall composition and synthesis conditions, and accordingly, the final concentrations of Co and Al in the second composition can also vary from secondary particle to secondary particle and within a single secondary particle, while still being greater than the concentrations of Co and Al in the first composition. It is therefore most useful to specify the amounts of Co and Al added to the grain boundaries relative to the first composition.
The amounts of Co and Al provided in the process solution (process solution) are considered as the average amounts of Co and Al added to the secondary particles and distributed throughout the grain boundaries of the secondary particles and are given relative to M of the first composition. When manufacturing the secondary particles described herein, it was found that almost all Co and Al in the process solution attached to the particles before calcination. Thus, the amount of Co and Al that can be used to enrich the grain boundaries is the amount in the process solution. Thus, when describing a process solution of, for example, 1 at% Al and 2 at% Co, this listed at% is relative to the amount of M in the first composition prior to grain boundary enrichment. Thus, at% of Al and Co in the process solutions used herein is always relative to the total M in the primary particles to be grain boundary enriched.
The amount of Al in the process solution is optionally 0.01 at% to 10 at%, optionally 9 at% or less, optionally 8 at% or less, optionally 7 at% or less, optionally 6 at% or less, optionally 5 at% or less, optionally 4 at% or less, optionally 3 at% or less, optionally 2 at% or less, optionally 1 at% or less, optionally 0.1 to 1 at%, optionally 0.5 to 1 at%. Optionally, the amount of Al in the process solution is equal to or less than 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5 atomic percent.
Optionally, the amount of Co in the process solution is greater than 3 at% and up to 4 at%, and the amount of Al is less than 1 at%, optionally 0.1 to 1 at%, optionally 0.1 to less than 1 at%. Optionally, the amount of Co in the process solution is 0.5 at% to 4 at% and the amount of Al is 0.01 at% to 10 at%.
In some aspects, the amount of Co in the process liquid is about 3 at%. At this Co concentration, the Al content is optionally less than 1 at%. An Al content of about 0.3 at% to 0.7 at%, optionally about 0.5. 0.5 at% is most suitable for reducing impedance growth during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 3.5 at%. At this Co level, the Al level is optionally less than 1 at%. An Al amount of about 0.3 to 0.7 at%, optionally about 0.5 at% is most suitable for reducing impedance growth during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 4 at%. At this Co concentration, the Al content is optionally less than 1.5 at%. An Al amount of about 0.7 to 1.3 at%, optionally about 1.0 at% is most suitable for reducing impedance growth during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 4.5 at%. At this Co concentration, the Al content is optionally less than 1 at%. An Al content of about 0.3 to 0.7, optionally about 0.5 at%, is most suitable for reducing the impedance increase during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 3 at%. At this Co concentration, the Al content is optionally less than 1.5 at%. An Al amount of about 0.5 to 1.3 at%, optionally about 1.0 at% is most suitable for reducing impedance growth during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is from about 3 at% to about 4 at%. At this Co concentration, the Al content is optionally less than 1 at%. An Al amount of about 0.3 to 0.1.3, optionally about 0.5 at% or about 1.0 at% is most suitable for reducing the impedance increase during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 3 at%. At this Co concentration, the Al content is optionally less than 1.5 at%. An Al content of about 0.5 to 1.3 at% is most suitable for reducing the impedance increase during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
In some aspects, the amount of Co in the process liquid is about 4 at%. At this Co concentration, the Al content is optionally less than 1.0 at%. An Al content of about 0.5 to 0.7 at% is most suitable for reducing the impedance increase during cycling. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
Thus, in some aspects, as the amount of Co increases from 3 at% to 4 at%, the amount of Al that produces the greatest improved results shifts from less than 1.3 at% to less than 0.7 at%. Optionally, al is substantially uniformly distributed in the plurality of secondary particles.
Optionally, as represented by some aspects of the secondary particles described herein, the amount of Al in the second composition is equal to or less than 100 at% relative to the amount of Co, meaning that the amount of Al is optionally equal to or less than the amount of Co. Optionally, the Al amount is less than 90 at%, optionally less than 80 at%, optionally less than 70 at%, optionally less than 60 at%, optionally less than 50 at%, optionally less than 40 at%, optionally less than 30 at%, optionally less than 20 at%, optionally less than 10 at%, optionally less than 9 at%, optionally less than 8 at%, optionally less than 7 at%, optionally less than 6 at%, optionally less than 4 at%, optionally less than 3 at%, optionally less than 2 at%, optionally less than 1 at% relative to the Co amount. It was found that Co amounts greater than Al amounts can achieve synergistic relationships that unexpectedly reduce the impedance increase compared to Co alone at the same or higher concentrations.
Optionally, among the plurality of secondary particles, al present in the second composition or throughout a portion or the entire grain boundary is substantially uniform. For example, when Al is introduced by the methods provided herein for grain boundary enrichment of Al only, powder EDS performed by standard techniques observe that there are "hot spots" rich in Al, indicating that Al is unevenly or inefficiently absorbed into the grain boundaries, resulting in separate phases of Al. But in the presence of Co and Al in the concentrations described herein in the process solution, the result is a much more uniform Al distribution, indicating that there is little or no hot spot observed by EDS. In some aspects, the number and/or size of Al hot spots is reduced by 50% or more, optionally 60% or more, optionally 70% or more, optionally 80% or more, relative to the Al grain boundary enrichment in the absence of Co enrichment.
Aluminum uniformity can also be assessed by comparing EDS at both magnifications. Table 2 of example 1 shows the aluminum concentration by EDS over a wide area (about 150 μm X150 μm) as the first value in the table, followed by the second value, which is an average EDS analysis over a much narrower area (about 1 μm X1 μm) concentrated on particles without significant hot spots. When 4% cobalt is used in the process liquid, these two values are close. But when cobalt is not used, the narrow areas of the non-hot spot have much less aluminum than the wider areas, indicating that much more aluminum is concentrated in the hot spot rather than being uniformly distributed among the many secondary particles.
In some aspects, M in the second composition further comprises one or more Ni-substituted elements (substitutional elements). The Ni substitution element is optionally a metal and is not Co or Al, as the presence of these elements results in the observed synergistic decrease in the increase in resistance. Optionally, the substitution element may include either Mg, mn, ca, sr, zn, ti, zr, hf, Y, cr, mo, W, fe, V, nb, ta, si, ga or one or more of B. The substitution element of the second composition may be present in an amount of about 1 to about 90 at%, specifically about 5 to about 80 at%, more specifically about 10 to about 70 at%, of the first composition. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, particularly about 2 to about 18 at%, more particularly about 4 to about 16 at%, of the first composition.
Optionally, the Li in the second composition need not be entirely Li, but may be partially substituted with one or more Li substitution elements selected from Mg, sr, na, K and Ca. The one or more Li-substituted elements are optionally present at 10 atomic% or less, optionally 5 atomic% or less, optionally 3 atomic% or less, optionally no more than 2 atomic%, wherein the% is relative to the total Li in the finished material (as-MADE MATERIAL).
The secondary particles provided herein may be prepared by synthesizing a green body from at least two components, optionally in powder form. The at least two components may comprise micronized (or non-micronized) lithium hydroxide or a hydrate thereof and a precursor hydroxide comprising nickel and optionally one or more other elements, and wherein the precursor hydroxide is optionally obtained by a co-precipitation process. It will be appreciated that the final overall composition (although not necessarily the distribution) of the elements in the final particles may be adjusted by increasing or decreasing the relative amounts of precursor materials in the formation of the green body. In some aspects, the lithium hydroxide or a hydrate thereof is micronized. Two or more powders forming the green body may be combined and shaken on a paint shaker to thoroughly mix the precursors. The green body is then calcined to a maximum temperature with controlled air or pure oxygen atmosphere. Calcination optionally follows a heating profile. The calcined product can then be processed to form a free flowing powder.
In some aspects, the precursor hydroxide may be a mixed metal hydroxide. In some aspects, the mixed metal hydroxide may include a metal composition of Ni, co, and Mg. Optionally, the mixed metal hydroxide comprises 10-100 at% Ni, 0-15 at% Co, and 0-5 at% Mg as metal components. Optionally, the mixed metal hydroxide comprises 10-100 at% Ni, 0-30 at% Co, and 0.1-80 at% Mn. Optionally, the mixed metal hydroxide comprises 10-100 at% Ni, 0-30 at% Co, and 0-10 at% Al. Optionally, the metal of the mixed metal hydroxide is 92 at% Ni and 8 at% Co. Optionally, the metal of the mixed metal hydroxide is 90 at% Ni, 8 at% Co and 2 at% Mg. Optionally, the metal of the mixed metal hydroxide is 89 at% Ni, 8 at% Co, 3 at% Mg. Optionally, the metal of the mixed metal hydroxide is 91 at% Ni, 8 at% Co, and 1 at% Mg. Optionally, the metal of the mixed metal hydroxide is 100 at% Ni. For example, the precursor hydroxide may be manufactured by a precursor supplier, such as Hunan Brunp Recycling Technology co.
The secondary particles may be formed by a multi-step process whereby particles of the first material are formed and calcined to establish the formation of distinct grain boundaries, optionally with the formation of particles having small amounts of defectsPrimary particles of NaFeO 2 structure. The particles are then subjected to a liquid process which applies Co and Al at the desired concentration levels, followed by drying and secondary calcination to selectively move the Co and Al precipitate species at the surface into the grain boundaries, thereby forming secondary particles with higher Co and Al concentrations in the grain boundaries than in the crystallites. According to a method of making secondary particles having Ni, co, and Mg substrates provided herein as one example, a forming process may include combining a lithium compound and one or more metal or metalloid hydroxide precursor compounds (e.g., previously formed combined Ni, co, and Mg, such as formed by a coprecipitation reaction) to form a mixture, heat treating the mixture at about 30 to about 200 ℃ to form a dry mixture, heat treating the dry mixture at about 200 to about 500 ℃ for about 0.1 to about 5 hours, and then heat treating at 600 ℃ to less than about 800 ℃ for about 0.1 to about 10 hours to make secondary particles. The maximum temperature of the primary calcination (first calcination) is relative and specific to the material used in the hydroxide precursor. Optionally, in one calcination, the maximum temperature may be equal to or less than 850 ℃, optionally equal to or less than 720 ℃, optionally equal to or less than 715 ℃, optionally equal to or less than 710 ℃, optionally equal to or less than 705 ℃, optionally equal to or less than 700 ℃. Optionally, the maximum temperature of the primary calcination may be about 680 ℃ or less. Optionally, the maximum temperature may be about 660 ℃ or less. Optionally, the maximum temperature may be about 640 ℃ or less. In still other aspects, the maximum temperature may be less than about 700 ℃, about 695 ℃, about 690 ℃, about 685 ℃, about 680 ℃, about 675 ℃, about 670 ℃, about 665 ℃, about 660 ℃, about 655 ℃, about 650 ℃, about 645 ℃, or about 640 ℃. The residence time at maximum temperature is optionally less than 10 hours. Optionally, the residence time at maximum temperature is less than or equal to 8 hours, optionally less than or equal to 7 hours, optionally less than or equal to 6 hours, optionally less than or equal to 5 hours, optionally less than or equal to 4 hours, optionally less than or equal to 3 hours, optionally less than or equal to 2 hours.
After calcination, subsequent processing may include pulverizing the calcined material with a mortar and pestle to pass the resulting powder through a desired screen, optionally a #35 screen. The powder is optionally subsequently tank milled in a1 gallon tank containing 2 cm drum YSZ media for optionally 5 minutes or sufficient time to allow the material to pass through an optional #270 sieve.
The primary calcined product or ground product may be subsequently processed, optionally in a process that produces enriched grain boundaries after secondary calcination. The process of enriching the grain boundaries within the primary particles may be carried out using the methods or compositions shown in U.S. Pat. nos. 9,391,317 and 9,209,455, except that the application process uses a liquid solution comprising a content of Co and a content of Al, optionally such that a synergistic enrichment of Co and Al occurs in the grain boundaries of the secondary particles. Grain-boundary-enriching element (ENRICHING ELEMENT) may optionally be applied by suspending the ground product in an aqueous slurry comprising Co, al and lithium compounds, optionally at a temperature of about 60 ℃, whereby Co and Al are present in the aqueous solution at the concentrations described herein. The slurry may then be spray dried to form a free flowing powder, which is then subjected to a secondary calcination (second calcination), optionally with a heating profile following a two step ramp up/dwell process. The first ramp/residence temperature curve in the two steps may be from ambient temperature (about 25 ℃) to 450 ℃ and optionally residence at 450 ℃ for 1 hour at a rate of 5 ℃ per minute. Subsequently, the second ramp/dwell may be from 450 ℃ to a maximum temperature at a rate of 2 ℃ per minute, with a dwell time of 2 hours at the maximum temperature. In some aspects, the maximum temperature is less than about 725 ℃, optionally about 700 ℃. In other aspects, the maximum temperature is about 725 ℃, optionally 750 ℃.
By combining a primary calcination with a maximum temperature as described above with a process of applying a grain boundary enrichment element followed by a secondary calcination also as described above, the resulting particles were found to be useful in cathodes to produce significantly improved reduction in resistance enhancement and/or reduction in capacity fade. Such a combination was found to bring about an additional cycle life and a reduced impedance increase, significantly improving the electrochemical performance of the material. Thus, it will be appreciated that in some aspects, the particles comprise a plurality of crystallites having a first composition comprising a polycrystalline layered structure lithiated metal oxide defined by the composition Li 1+xMO2+y, wherein-0.1 +.0.3 and-0.3 +.y +.0.3. In some aspects, x is-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.30. In some aspects, y is-0.3, optionally-0.2, optionally-0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is greater than or equal to -0.30、-0.29、-0.28、-0.27、-0.26、-0.25、-0.24、-0.23、-0.22、-0.21、-0.20、-0.19、-0.18、-0.17、-0.16、-0.15、-0.14、-0.13、-0.12、-0.11、-0.10、-0.09、-0.08、-0.07、-0.06、-0.05、-0.04、-0.03、-0.02、-0.01、0.00、0.01、0.02、0.03、0.04、0.05、0.06、0.07、0.08、0.09、0.10、0.11、0.12、0.13、0.14、0.15、0.16、0.17、0.18、0.19、0.20、0.21、0.22、0.23、0.24、0.25、0.26、0.27、0.28、0.29 or 0.3. The crystallites have Ni in an amount of 10 atomic% to 100 atomic% (at%) of the M element. Optionally, the Ni component of M is greater than or equal to 75 at%. Optionally, the Ni component of M is 80 at% or greater. Optionally, the Ni component of M is greater than or equal to 85 at%. Optionally, the Ni component of M is greater than or equal to 90 at%. Optionally, the Ni component of M is greater than or equal to 95 at%. Optionally, the Ni component of M is 75 at%、76 at%、77 at%、78 at%、79 at%、80 at%、81 at%、82 at%、83 at%、84 at%、85 at%、86 at%、87 at%、88 at%、89 at%、90 at%、91 at%、92 at%、93 at%、94 at%、95 at%、96 at%、98 at%、99 at% or greater than or equal to 100 at%. The M-component may include one or more additional elements. The additional element is optionally a metal. Optionally, the additional elements may include either Al, mg, co, mn, ca, sr, zn, ti, Y, cr, mo, fe, V, si, ga or one or more of B. In particular aspects, the additional elements may include Mg, co, al, or a combination thereof. Optionally, the additional element may be Mg, al, V, ti, B or Mn or a combination thereof. Optionally, the additional element consists of Mg, al, V, ti, B or Mn. In some aspects, the additional element is Mn or Mg, or Mn and Mg. The additional elements of the first composition may be present in an amount of from about 1 to about 90 at%, particularly from about 5 to about 80 at%, more particularly from about 10 to about 70 at%, of the first composition. Optionally, the additional element may be present in an amount of about 1 to about 20 at%, particularly about 2 to about 18 at%, more particularly about 4 to about 16 at%, of the first composition. In some illustrative examples, M is about 75-100 at% Ni, 0-15 at% Co, 0-15 at% Mn, and 0-10 at% additional elements. The resulting secondary particles have grain boundaries in which the amount of Co and the amount of Al are greater than in crystallites.
The resulting particles optionally exhibit a reduction in resistance increase as compared to particles having only Co-enriched grain boundaries, optionally at Co content that is considered insufficient to significantly improve the cycling characteristics of the particles without Co-enrichment at the grain boundaries. When the resulting secondary particles are the active material of the cathode of a Li-ion battery, the battery cycled between 4.2V and 2.7V at 45 ℃ optionally exhibits an impedance increase of less than 50% in the fully charged (4.2V) state for more than 50 cycles, optionally more than 60 cycles, optionally more than 70 cycles, optionally more than 80 cycles, optionally more than 90 cycles, optionally more than 100 cycles, optionally more than 110 cycles, optionally more than 120 cycles, optionally more than 130 cycles, optionally more than 140 cycles, optionally more than 150 cycles, optionally more than 200 cycles.
In other aspects, a cell cycled between 4.2V and 2.7V at 45 ℃ optionally exhibits an impedance increase in a fully charged (4.2V) state of less than 100% for more than 100 cycles, optionally more than 110 cycles, optionally more than 120 cycles, optionally more than 130 cycles, optionally more than 140 cycles, optionally more than 150 cycles, optionally more than 160 cycles, optionally more than 170 cycles, optionally more than 180 cycles, optionally more than 190 cycles, optionally more than 200 cycles, optionally more than 210 cycles, optionally more than 220 cycles.
In other aspects, a battery cycled between 4.2V and 2.7V at 45 ℃ optionally exhibits less than 50% impedance increase at 50% state of charge (SOC) for greater than 200 cycles, optionally less than 40% for greater than 200 cycles, optionally less than 30% for greater than 200 cycles.
The electrochemical cells provided herein optionally use the particles provided herein as an electrochemically active material, optionally having an initial discharge capacity of 180 mAh/g particles or greater, optionally 185 mAh/g, optionally 190 mAh/g, optionally 195 mAh/g, optionally 200 mAh/g, optionally 210 mAh/g.
According to what is shown in fig. 1, a particle is disclosed comprising crystallites 10 comprising a first composition and grain boundaries 20, 21 comprising a second composition, wherein the Al concentration in the grain boundaries is greater than the Al concentration in the crystallites and the cobalt concentration in the grain boundaries is greater than the cobalt concentration in the crystallites. The particles comprise a plurality of crystallites and are referred to as secondary particles. An outer layer, such as a passivation layer or protective layer, shown at 30 in fig. 1, may optionally be deposited on the outer surface of the particles. The outer layer may completely or partially cover the secondary particles. The layer may be amorphous or crystalline. The layer may comprise an oxide, phosphate, pyrophosphate, fluorophosphate, carbonate, fluoride, oxyfluoride, or combination thereof of an element such as Al, ti, B, li, or Si, or a combination thereof. In some aspects, the outer layer comprises borates, aluminates, silicates, fluoroaluminates, or combinations thereof. Optionally, the outer layer comprises carbonate. Optionally, the outer layer comprises ZrO2、Al2O3、TiO2、AlPO4、AlF3、B2O3、SiO2、Li2O、Li2CO3 or a combination thereof. Optionally, the outer layer comprises either AlPO 4 or Li 2CO3. The layer may be deposited by any method or technique that does not adversely affect the desired properties of the particles. Representative methods include, for example, spray coating and dip coating.
Also provided are electrodes comprising the secondary particles described herein as a component of or the sole electrochemically active material. The active component optionally as a cathode comprises the secondary particles provided herein. The cathode optionally includes the secondary particles disclosed above as an active material and may further include a conductive agent and a binder. The conductive agent may include any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may include carbon black, such as acetylene black or lamp black, mesophase carbon (mesocarbon), graphite, graphene, carbon fibers, carbon nanotubes, such as single-walled carbon nanotubes or multi-walled carbon nanotubes, or combinations thereof. The binder may be any binder that provides suitable properties and may include, for example, polyvinylidene fluoride, copolymers of polyvinylidene fluoride and hexafluoropropylene, poly (vinyl acetate), poly (vinyl butyral-co-vinyl alcohol-co-vinyl acetate), poly (methyl methacrylate-co-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-co-vinyl acetate, polyvinyl alcohol, poly (l-vinylpyrrolidone-co-vinyl acetate), cellulose acetate, polyvinylpyrrolidone, polyacrylate, polymethacrylate, polyolefin, polyurethane, polyvinyl ether, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene/ethylene-butylene/styrene triblock polymers, polyethylene oxide, or combinations thereof.
The cathode may be manufactured by combining the particles, conductive agent, and binder described herein in a suitable ratio, such as from about 80 to about 98 weight percent of the particles, from about 1 to about 20 weight percent of the conductive agent, and from about 1 to about 10 weight percent of the binder, based on the total weight of the particles, conductive agent, and binder. The particles, conductive agent and binder may be suspended in a suitable solvent, such as N-methylpyrrolidone, and disposed on a suitable substrate (such as aluminum foil) and dried in air. It is noted that the substrate and solvent are given for illustration only. Other suitable substrates and solvents may be used or combined to form the cathode.
The cathode provided herein optionally exhibits significantly reduced impedance growth when cycled in 2025 coin cells with MCMB 10-28 graphite anode, polyolefin separator, and electrolyte of 1M LiPF 6 in 1/1/1 (vol.) EC/DMC/EMC containing 1 wt% VC, as compared to Co-enriched only or no grain boundary enriched material. A measure of the increase in impedance can be obtained by cycling the battery at high rates, interspersed with 1C/1C charge/discharge cycles at 20 cycles intervals in the cycling scheme. 1C was charged to 4.2V and then held at a voltage during which time the battery voltage was held at 4.2V until the current decayed to C/10 rate, then the battery was allowed to stand under open circuit for 5 minutes. When a fully charged battery is subsequently discharged, its voltage drop and 1C discharge rate experienced during the first 10 seconds of discharge are input to ohm's law (v=ir) to calculate a DCR (direct current resistance) measurement of the battery impedance. Impedance measurements plotted against cycle number yield a curve with a specified slope. When the active particle material has grain boundaries enriched in Co and Al as described herein, the impedance slope is lower compared to particles without such grain boundary enrichment or compared to particles with grain boundaries enriched in Co only. In some aspects, the impedance increase of the battery is equal to or less than 25% for the first 50 cycles, optionally 50% or less for the first 100 cycles, optionally 63% or less for the first 125 cycles, optionally 75% or less for the first 150 cycles. Optionally, the impedance increase is equal to or less than 25% over 50 cycles, optionally 50% or less over 100 cycles, optionally 63% or less over 125 cycles, optionally 75% or less over 150 cycles.
A battery including the cathode is also disclosed. The battery may be, for example, a lithium ion battery, a lithium-polymer battery, or a lithium battery. The battery may include a cathode, an anode, and a separator interposed between the cathode and the anode. The separator may be a microporous membrane (microporous membrane) and may include a porous membrane (porous film) comprising polypropylene, polyethylene, or a combination thereof, or may be a woven or nonwoven material, such as a glass fiber mat. The anode may include a coating on the current collector. The coating may comprise a suitable carbon, such as graphite, coke, hard carbon, or mesophase carbon, for example mesophase carbon microspheres. The current collector may be, for example, copper foil.
The battery also includes an electrolyte that can contact the positive electrode (cathode), the negative electrode (anode), and the separator. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a linear or cyclic carbonate. Representative organic solvents include ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate,-Butyrolactone, sulfolane, 1, 2-dimethoxyethane, 1, 2-diethoxyethane, tetrahydrofuran, 3-methyl-l, 3-dioxolane, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, dimethyl carbonate, diethyl carbonate, methylethyl carbonate, dipropyl carbonate, methylpropyl carbonate, propane sultone or a combination thereof. In another aspect, the electrolyte is a polymer electrolyte.
Representative lithium salts that may be used in the electrolyte include, but are not limited to LiPF6、LiBF4、LiAsF6、LiClO4、LiCF3SO3、Li(CF3SO2)2N、LiN(SO2C2F5)2、LiSbF6、LiC(CF3SO2)3、LiC4F9SO3 and LiAlCl 4. The lithium salt may be dissolved in an organic solvent. Combinations comprising at least one of the foregoing can be used. The concentration of lithium salt in the electrolyte may be 0.1 to 2.0M.
The electrolyte may be a solid ceramic electrolyte.
The battery pack may have any suitable configuration or shape and may be cylindrical or square.
Various aspects of the present disclosure are illustrated by the following non-limiting examples. These examples are intended to illustrate and not limit any practice of the invention. It is to be understood that variations and modifications may be made without departing from the spirit and scope of the invention.
Examples
Example 1 polycrystalline 2D alpha-NaFeO 2 -type lamellar particles enriched in Al and Co at the grain boundaries
Electrochemically active polycrystalline 2D alpha-NaFeO 2 layered structure particles with or without different types of grain boundary enrichment and each having high nickel in the cathode material are prepared.
By dry mixing 252.1 grams of Li (OH) 2 (dehydrated, micronized LiOH from FMC in a1 liter tankH 2O)、961.6 Ni0.91Co0.08Mg0.01(OH)2 (custom) a material of composition Li 1.03Mg0.01Ni0.92Co0.08O2 was prepared. The compounds were mixed by shaking the jar in a paint shaker.
The mixed compound was placed in an alumina crucible and sintered. Sintering is performed by heating to about 450 ℃ at a rate of about 5 ℃ per minute and held at about 450 ℃ for about 2 hours. The temperature was then increased to about 700 ℃ at about 2 ℃ per minute and maintained for about 6 hours. The sample was then allowed to cool naturally to room temperature. The cooled sample was ground for approximately 5 minutes to break up any agglomerates to provide Li 1.03Mg0.01Ni0.92Co0.08O2. Analysis of the material by XRD confirmed-NaFeO 2 type structure.
Samples of 100 grams each of Co and Al grain boundary enriched secondary particles were prepared using the above base materials. Li, co and Al nitrates were dissolved in 100 grams of H 2 O heated to 60 ℃. The amounts of Al and Co added correspond to 1.9 at% and 4 at%, respectively, relative to ni+co in the Li 1.03Mg0.01Ni0.92Co0.08O2 first composition. The amount of LiNO 3 formulated was such that the final Li/transition metal+Al ratio was 1.01.
To this was added 100 g of Li 1.03Mg0.01Ni0.92Co0.08O2 prepared as above and the resulting slurry was stirred for 30 to 120 minutes. The slurry is then spray dried to produce a powder. The resulting powder was placed in an alumina crucible and heated to about 450 ℃ at a rate of about 5 ℃ per minute and held at about 450 ℃ for about 1 hour. The temperature was then increased to about 700 ℃ at about 2 ℃ per minute and maintained for about 2 hours. The materials were then allowed to cool naturally to 100 ℃. The calcined material was first separately ground in a mortar and pestle and then in a pot mill.
In general, four materials with or without grain boundary enrichment of Al and/or Co were prepared using the procedure described above with the final overall composition shown in table 1 (based on their synthetic formulation).
Table 1:
The resulting materials and control were each blended with a slurry of PVDF binder and conductive carbon in NMP solvent and coated onto an aluminum foil current collector. Similar coatings of the selected materials were also prepared on Cu foil so that they could be analyzed for Al distribution by FIB-STEM-EDS without the risk of measuring Al originating from the foil. The cathode electrode was then punched out of the foil and combined with MCMB 10-28 graphite anode, porous polypropylene separator and carbonate-based electrolyte in Li-ion "all" coin cell format for electrochemical cycle life testing. The cathode electrode was also combined with a lithium metal anode, a porous polypropylene separator and a carbonate-based electrolyte in a "half" coin cell format for electrochemical discharge capacity testing.
The full cell cycled through a series of charge and rapid discharge cycles at 45 ℃. The low-rate discharge capacity and the resistance value were measured every 20 charge/discharge cycles. Some materials were further analyzed by EDS and cross-sectional TEM/EDX prior to use in forming the cathode.
Figures 2 and 3 show the capacity fade (CAPACITY FADE) and associated impedance increase for a full cell cycled at 45 ℃. FIG. 2 shows that the "No Grain-Boundary-enrichment method (No Grain-Boundary-ENRICHING PROCESS)" (No slurry, spray-drying, or secondary calcination) and "No Grain-Boundary-enrichment element (No Grain-Boundary-ENRICHING ELEMENTS)" (No Co or Al solute in aqueous slurry, spray-drying, and secondary calcination) samples had capacity decaying at approximately the same high rate. The "no grain boundary enrichment element" material is subjected to an aqueous slurry and subsequent calcination process, but only with water that is free of grain boundary enrichment elements. Fig. 3 shows that these two materials also have similar resistance improvement rates, confirming that the water impregnation, spray drying and secondary calcination processes have no significant effect. The aluminum-only samples showed modest improvements over the baseline without grain boundary enrichment elements, but the most significant improvement was observed for the cobalt-only grain boundary enrichment, with 10% decay over 300 cycles.
Grain Boundary (GB) enriched cobalt and aluminum samples showed no improvement in capacity fade over cobalt alone. But as seen in fig. 3, it has a significantly lower impedance increase, about 50% after 100 cycles and about 115% after 200 cycles in the fully charged state. GB-rich Co and Al materials provide a 30% lower resistance increase than GB-rich Co alone and do not use any additional Co to achieve this.
Cobalt greatly improves the absorption of aluminum because in the absence of Co in the process solution, a separate phase of lithiated alumina was observed and shown in fig. 4, as shown by EDS mapping (EDS MAPPING) of the calcined material. The image below the EDS elemental profile for aluminum (bright spots) shows that the material formulated with only Al in the process solution has stronger and more Al "hot spots" than the material formulated with Co together with Al in the process solution, shows that the addition of Co to the process formulation causes the Al to be more evenly distributed between the many secondary particles and shows that Co causes much more Al to be absorbed by the particles when the particles are calcined.
The results of quantitative EDS by comparing the Al analysis for particles over a large area (about 150 μm x μm) with the results obtained by averaging the 3-point (about 1 μm x1 μm) analysis obtained at the non-hot spot location also show a more uniform Al distribution and absorption between the many secondary particles when formulated with Co in the process solution. Table 2 shows these comparisons for Al-only formulated and Al-Co formulated cathode particles and shows that localized non-hot spot analysis with Co and Al formulated yields Al content results similar to those obtained over a wide area, indicating that Al is substantially uniformly distributed among the many secondary particles. In contrast, al-only formulated materials have much lower non-hot spot Al analysis results than broad areas, indicating that a large amount of Al is concentrated in the hot spot particles rather than being uniformly distributed among the many secondary particles.
TABLE 2 EDS analysis results of cathode Material powders
Quantitative point analysis by STEM/EDS on thin layers of these two materials confirmed that inclusion of Co with Al in the process formulation promotes absorption of Al into the grain boundaries upon subsequent calcination. Secondary particles of each material coated on Cu foil as described above were sliced by Focused Ion Beam (FIB) milling to produce thin layers of about 100 nm a thick. Fig. 5 shows a Scanning Transmission Electron Microscopy (STEM) image of a small slice containing several crystallites from particles prepared by a grain boundary enrichment method in which 1.9 at% Al and 4 at% Co are formulated in a process liquid, and shows the locations where 3 EDS point analyses were performed, locations 1 and 3 being inside adjacent crystallites, location 2 being at the intervening grain boundary. Fig. 6 shows EDS spectra collected at the 3 positions marked in fig. 5. Spectrum 2 at the grain boundary showed a clear Al peak at about 1.5 keV, whereas spectra 1 and 3 inside the crystallites did not. As shown by comparing the 6.9 keV Co peak with the 8.3 keV Ni peak in each spectrum, spectrum 2 at the grain boundary also shows a higher Co/Ni ratio than seen in spectrum 1 and spectrum 3 inside the crystallites. The quantitative results obtained by integrating the spectra of fig. 6 are shown in table 3, which shows that the positions of the crystal grain boundaries of spectrum 2 are enriched with Al and Co.
TABLE 3 results of 3 EDS Point analysis of particles made with 1.9 at% Al, 4 at% Co process liquid material
ND is undetectable
The same type of STEM-EDS analysis was performed on particles prepared by the grain boundary enrichment method in the presence of 1.9 at% Al in the process solution in the absence of Co, and the locations of the STEM image and EDS point analysis are shown in fig. 7. The position of spectrum 1 is at the grain boundary and the position of spectrum 2 is inside the crystallites. Fig. 8 shows EDS spectra collected at the 2 positions marked in fig. 7, and neither spectrum indicates the presence of Al and there is little difference between their Co peaks. The quantitative results obtained by spectral integration of fig. 8 are shown in table 4 and show that the grain boundaries and bulk crystallites have the same composition, indicating that the secondary particles have little Al absorption (Al uptake) or grain boundary enrichment.
TABLE 4 results of 2 EDS Point analysis of only 1.9 at% Al in the process liquid
STEM-EDS point analysis of the type described above was performed at a total of 11 grain boundaries and 10 crystallite interior locations for 1.9 at% Al, 4 at% Co grain boundary enriched material, and 16 grain boundaries and 7 crystallite interior locations for only 1.9 at% Al enriched material. The average results of these analyses compared to the bulk formulated compositions (bulk formulated compositions) of these materials are given in table 5 and indicate that the application of the Al-only liquid process and subsequent calcination brings little to no Al enrichment of the grain boundaries (measurable amounts of Al were detected at 3 of the 16 sites), whereas processing with Al and Co and subsequent calcination resulted in significant enrichment of the grain boundaries for both elements.
TABLE 5 average EDS Point analysis results for grain boundaries (second composition) and crystallite interiors (first composition) of Co-enriched materials of 1.9 at% Al alone or 1.9 at% Al, 4.4 at% Co alone
Example 2 grain boundary enrichment of Al and Co by non-Crystal grain boundary enrichment method
Electrochemically active polycrystalline 2D alpha-NaFeO 2 -type layered structure particles having different types of grain boundary enrichment and each having high nickel in the cathode material are prepared by a non-crystal grain boundary enrichment method. A material having a composition of Li 1.03Mg0.01Ni0.92Co0.08O2 was prepared by the method of example 1. Then 30 grams of this material was dispersed in 40 ml of methanol containing 1.9 at% Al as dissolved nitrate with or without 4.4 at% cobalt nitrate and with sufficient LiNO 3 to give a final Li/transition metal + Al ratio of 1.01. The resulting slurry was rotary evaporated to dryness and the recovered material was then subjected to the same calcination procedure applied to the spray dried material in example 1. Fig. 9 shows the ai EDS mapping of the calcined material and shows that the material formulated with only ai has stronger and more ai "hot spots" than the material formulated with Co together with ai as seen for the aqueous process material in example 1. This result suggests that the effect of solution processing using Co in promoting more uniform absorption of Al by secondary particles is not an artifact of aqueous processes, and that non-aqueous deposition of grain boundary enrichment elements by solvent evaporation yields the same results as aqueous deposition by acid-base precipitation.
Example 3 synergistic benefits obtained by grain boundary enrichment of Al and Co
Electrochemically active polycrystalline 2D α -NaFeO 2 -type layered structure particles having different types of grain boundary enrichment and each having high nickel in the cathode material were prepared from Li 1.03Mg0.01Ni0.92Co0.08O2 base material by the method of example 1. The Al and Co process formulations used to make these materials are shown by the substrates in table 6.
TABLE 6 Al and Co content in the process solution used to make the grain boundary enriched material of example 3
Li-ion coin cells were constructed with the materials enriched in table 6 and cycled according to the method of example 1. Fig. 10 illustrates the cyclic capacity fade and their dependence on formulated Co content for cells using 0 at% Al grain boundary enriched material and using 0.5 at% Al grain boundary enriched material. As Co in the formulation increases, the capacities of the various materials decrease, but their capacity fade rates do not vary greatly, ranging from 4% to 6% over 200 cycles and are substantially unaffected by the inclusion or absence of 0.5 at% Al in the formulation. However, figure 11 shows that increasing the Co content in the formulation reduces the impedance increase, as the formulation Co content increases from 3 at% to 4 at%, the 4.2V impedance increase at 200 cycles decreases from 250% to 130%, and further including 0.5 at% Al in the solution process formulation significantly reduces the impedance increase at all Co content in the formulation, as the Co content in the solution process formulation increases from 3 at% to 4.5 at%, the impedance increase at 200 cycles decreases from 150% to 90%. Fig. 12 further demonstrates that the synergistic benefits observed by including Al in the solution process formulation, the amount of impedance reduction is greater than that obtainable by merely further increasing the Co concentration.
Fig. 13 shows the cyclic capacity fade (left) and impedance increase (right) for cells with cathode materials enriched by the 3 at% Co solution process formulation grain boundaries with different Al content. The graph shows that increasing the formulated Al content decreases the capacity of the cathode material without significantly affecting the capacity fade (all cells fade in the range of 6% -8% over 200 cycles), but increasing the formulated Al content from 0 at% to 1 at% decreases the 4.2V impedance increase from 200% to 120% over 200 cycles, while higher Al content causes a slight increase in impedance increase. The impedance increase plotted in fig. 13 is summarized in fig. 14, which shows that in the presence of 3 at% Co with Al in the process solution, the lowest impedance increase is obtained when the formulated Al/Co atomic% ratio of the process solution is about 0.3-0.4.
EXAMPLE 4 enrichment of Al and Co grain boundaries of NCA Material
Two NCA materials of similar overall composition were produced, one with Co and Al grain boundary enrichment and one without. In each case, the base material is produced by blending hydroxide precursors together and firing in an oxygen atmosphere until the final lithiated oxide is formed and sintered.
Material 1 NCA base Material with first composition LiNi 0.93Co0.04Al0.03O2 enriched with an additional 4: 4 at% Co, 0.6. 0.6 at% Al grain boundaries relative to the total M in the first composition
Precursor transition metal hydroxides are used in this process. It contains 4 at% Co and 3 at% Al and the balance Ni, calculated as transition metal. Micronized LiOH powder was produced by placing 51 grams LiOH together with 500 grams Y stabilized zirconia 1 ⁄ 4 "spheres in a plastic jar and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic jar containing 190.15 grams of transition metal hydroxide precursor and both powders were blended by shaking the jar on a paint shaker for an additional 10 minutes. After blending, approximately 240 grams of blended powder was split into two crucibles and fired in an oxygen atmosphere by first ramping up to 450 ℃ at 5 ℃/min and soaking at temperature for 2 hours and then ramping up to 680 ℃ at 2 ℃/min and soaking for 6 hours. When this heating sequence is completed, the furnace is allowed to cool to 130 ℃, the powder is removed and placed in a pot mill. The pot mill contained 1 ⁄ < 2 > drum media (drumstick) and was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve. Analysis of the material by XRD confirmed-NaFeO 2 type structure.
The powder was then coated with Co and Al by making a solution of 80 grams of water, 9.5 grams of cobalt nitrate (4 at% Co relative to total M in the LiMO 2 base composition), 1.9 grams of aluminum nitrate (0.6 at% Al relative to total M in the LiMO 2 base composition), 2.7 grams of lithium nitrate, and heating to 60 ℃. To this was added 80 grams of the previously prepared powder. The slurry was stirred for 25 minutes after which it was spray dried to remove water from the slurry and prepare a dry powder. This powder was then fired in an air atmosphere by first heating to 450 ℃ and soaking for 1 hour at 5 ℃ and then heating to 700 ℃ and soaking for 2 hours at 2 ℃ per minute. The furnace was then allowed to cool to 130 ℃, the powder was removed from the furnace and sieved through a 270 mesh screen. Fig. 15 shows STEM micrographs of thin-cut secondary particles of the material thus prepared coated on Cu foil as described in example 1. FIG. 15 also provides Al/Ni and Co/Ni atomic ratio results of 3 EDS point analyses of the internal Grain Boundaries (GB) and bulk regions of adjacent primary particles, indicating that the grain boundaries are enriched in Co and Al.
Material 2 comparative NCA base Material with homogeneous first composition LiNi 0.89Co0.08Al0.03O2
Precursor transition metal hydroxides are used in this process. It contains 8 at% Co and 3 at% Al with the balance Ni. Micronized LiOH powder was produced by placing 25.5 grams LiOH with 500 grams Y stabilized zirconia 1 ⁄ "spheres in a plastic jar and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic jar containing 95.1 grams of transition metal hydroxide and the two were blended by shaking the jar on a paint shaker for an additional 10 minutes. After blending, approximately 120 grams of the powder was placed in a crucible and fired in an oxygen atmosphere by first ramping up to 450 ℃ at 5 ℃ per minute and soaking at temperature for 2 hours and then ramping up to 680 ℃ at 2 ℃ per minute and soaking for 6 hours. The furnace was then allowed to cool to 130 ℃, the powder was removed and placed in a pot mill. The pot mill contained 1 ⁄ < 2 > drum media (drumstick) and was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve. Analysis of the material by XRD confirmed-NaFeO 2 type structure.
The cathode materials 1 and 2 described above were assembled in a button cell as described in example 1. The cell was cycled 1C/1C at 45 ℃, with DCR discharged at 100% state of charge (SOC) per cycle and 10 seconds measured at 50% SOC per 20 cycles. The capacity fade and impedance increase results for a 2-cell Li-ion coin cell made with each material are shown in fig. 16 and 17, respectively. Although the overall composition of the two materials is nearly equal, grain boundary enriched material #1 contains Co enriched in grain boundaries between bulk crystallites, while material #2 contains an equal total amount of Co uniformly distributed throughout the secondary particles. Material #1 has only a slightly higher total Al content than material #2, but the extra Al (16% more Al than material # 2) is concentrated at the grain boundaries. Both capacity fade and resistance increase of GBE materials are greatly improved over materials of uniform composition. Fig. 16 shows that grain boundary enriched material #1 has only 8% capacity fade over 200 cycles in addition to slightly higher capacity (1%) than homogeneous material #2, which is >30% fade. Fig. 17 shows that the cell with grain boundary enriched material #1 had 100% resistance increase at full SOC (4.2V) and 30% resistance increase at 50% SOC after 200 cycles, while the cell with material #2 had >800% resistance increase at full SOC and >200% resistance increase at 50% SOC after 200 cycles.
EXAMPLE 5 enrichment of Al and Co grain boundaries of NCM Material
An NCM base material (NCM 811) having a first composition LiNi 0.8Co0.1Mn0.1O2 was prepared from a Co-precipitated precursor transition metal hydroxide containing 10 at% Co and 10 at% Mn and the balance Ni. Micronized LiOH powder was produced by placing 87.7 grams LiOH together with 500 grams Y stabilized zirconia 1 ⁄ "spheres in a plastic jar and shaking on a paint shaker for 45 minutes. This micronized powder was then transferred to another plastic tank containing 335.7 grams of precursor transition metal hydroxide and the two were blended by shaking on a paint shaker for an additional 10 minutes. After blending, approximately 440 grams of powder was split into three crucibles and fired in an oxygen atmosphere by first ramping up to 450 ℃ at 5 ℃ per minute and soaking at temperature for 2 hours and then ramping up to 770 ℃ at 2 ℃ per minute and soaking at 770 ℃ for 10 hours. The furnace was then allowed to cool to 130 ℃, the powder was removed and placed in a pot mill. The pot mill contained 3 ⁄ 4 "drum media (drumstick) and was used to grind the powder for 2 minutes. The powder was then sieved through a 270 mesh sieve.
The powder was then separated into a base material (without further treatment) or grain boundaries enriched with Co and Al by making a solution of 200 grams of water, 11.9 grams of cobalt nitrate (2 at% Co relative to the base composition), 3.1 grams of aluminum nitrate (0.4 at% Al), 3.4 grams of lithium nitrate and heating to 60 ℃. 200 grams of the lithiated precursor powder previously prepared was added thereto. The slurry was stirred for 10 minutes after which it was spray dried to remove water from the slurry and prepare a dry powder. This powder was then fired in an air atmosphere by first ramping up to 450 ℃ at 5 ℃ per minute and soaking at temperature for 1 hour and then ramping up to 770 ℃ at 2 ℃ per minute and soaking for 0.25 hour. The furnace was then allowed to cool to 130 ℃, the powder was removed from the furnace and sieved through a 270 mesh screen. The overall composition of the synthesized cathode powder was LiNi 0.079Co0.11Mn0.09Al0.006O2.
The above substrate and grain boundary enriched NCM material were then assembled in Li-ion coin cells, which were cycled at 45 ℃ by the methods described in examples 1 and 4. The capacity fade and impedance increase results for a 2-cell Li-ion coin cell made with each material are shown in fig. 18 and 19, respectively. Both materials had good cycling stability (fig. 18), the grain boundary enriched material decayed slightly lower (about 4% decay vs. about 5% decay of the base material over 200 cycles) and had slightly lower initial capacity. Nevertheless, the grain boundary enriched material had a much lower resistance increase than the homogeneous base material of similar composition (fig. 19), 45% resistance increase at 100% SOC and 38% resistance increase at 50% SOC after 200 cycles, in contrast to 225% resistance increase at 100% SOC and 70% resistance increase at 50% SOC after 200 cycles. These results demonstrate that grain boundary enrichment with relatively low amounts of Al and Co is beneficial for NCM.
Various modifications in addition to those shown and described herein will be apparent to those skilled in the art from the foregoing description. Such modifications are also intended to fall within the scope of this disclosure.
It will be appreciated that unless otherwise specified, all reagents may be obtained from sources known in the art.
Patents, publications and applications mentioned in the specification are indicative of the levels of those skilled in the art to which the disclosure pertains. These patents, publications, and applications are incorporated herein by reference as if each individual patent, publication, or application was specifically and individually indicated to be incorporated by reference.
The above description is illustrative of particular aspects of the invention and is not intended to be limiting in its practice.

Claims (51)

1.一种粒子,其包含:1. A particle comprising: 包含含锂、镍和氧的第一组合物的许多微晶;Contains numerous microcrystals of a first composition containing lithium, nickel, and oxygen; 在所述许多微晶的相邻微晶之间并包含具有层状-NaFeO2型结构、立方结构、尖晶石结构或其组合的第二组合物的晶粒边界;Between adjacent microcrystals of the plurality of microcrystals and comprising a layered structure -Grain boundaries of a second composition of NaFeO2 type structure, cubic structure, spinel structure or combinations thereof; 其中晶粒边界中的铝浓度大于微晶中的铝浓度,且任选地,其中晶粒边界中的钴浓度大于微晶中的钴浓度。The aluminum concentration at the grain boundaries is greater than that in the microcrystals, and optionally, the cobalt concentration at the grain boundaries is greater than that in the microcrystals. 2.权利要求1的粒子,其中铝在所述许多粒子中基本均匀分布。2. The particles of claim 1, wherein aluminum is substantially uniformly distributed among the plurality of particles. 3.权利要求1的粒子,其中晶粒边界中的铝量为相对于第一组合物中的总过渡金属计0.01 at%至10 at%。3. The particles of claim 1, wherein the amount of aluminum at the grain boundaries is from 0.01 at% to 10 at% relative to the total transition metals in the first composition. 4.权利要求1的粒子,其中第二组合物中的铝浓度等于或小于第二组合物中的Co浓度。4. The particles of claim 1, wherein the aluminum concentration in the second composition is equal to or less than the Co concentration in the second composition. 5.权利要求1-4任一项的粒子,其中所述许多微晶具有α-NaFeO2型层状结构、立方结构、尖晶石结构或其组合。5. The particles of any one of claims 1-4, wherein the plurality of microcrystals have an α- NaFeO2 type layered structure, a cubic structure, a spinel structure, or a combination thereof. 6.权利要求1-4任一项的粒子,其中所述微晶包含由Li1+xMO2+y界定的第一组合物,其中6. The particles of any one of claims 1-4, wherein the microcrystals comprise a first composition defined by Li <sub>1+x</sub> MO <sub>2+y </sub>, wherein -0.1≤x≤0.3,-0.1 ≤ x ≤ 0.3, -0.3≤y≤0.3和-0.3 ≤ y ≤ 0.3 and 其中M包含大于或等于10原子%的镍。M contains 10 atomic percent or more of nickel. 7.权利要求6的粒子,其中M包含大于或等于75 at%的镍的原子%。7. The particle of claim 6, wherein M comprises 75 at% or more of nickel atoms. 8.权利要求1-4任一项的粒子,其中晶粒边界包含相对于第二组合物中的总过渡金属计大约2 at%至大约99 at%的量的钴和相对于第二组合物中的总过渡金属计大约0.5 at%至大约99 at%的量的铝。8. The particles of any one of claims 1-4, wherein the grain boundaries comprise cobalt in an amount of about 2 at% to about 99 at% relative to the total transition metals in the second composition and aluminum in an amount of about 0.5 at% to about 99 at% relative to the total transition metals in the second composition. 9.权利要求6的粒子,其中9. The particle of claim 6, wherein M进一步包含附加金属,其中所述附加金属以大约1 at%至大约90 at%的量存在;M further comprises an additional metal, wherein the additional metal is present in an amount of about 1 at% to about 90 at%; 所述附加金属选自Mg、Sr、Co、Al、Ca、Cu、Zn、Mn、V、Ba、Zr、Ti、Cr、Fe、Mo、B和它们的任何组合。The additional metal is selected from Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof. 10.权利要求6的粒子,其中所述微晶包含钴,钴浓度在相对于第一组合物中的总过渡金属计0 at%至大约50 at%、任选相对于第一组合物中的总过渡金属计1 at%至大约50 at%的范围内。10. The particles of claim 6, wherein the microcrystals comprise cobalt, the cobalt concentration being in the range of 0 at% to about 50 at% relative to the total transition metals in the first composition, optionally from 1 at% to about 50 at% relative to the total transition metals in the first composition. 11.权利要求6的粒子,其中所述微晶包含钴,钴浓度在相对于第一组合物中的总过渡金属计1 at%至大约10 at%的范围内。11. The particles of claim 6, wherein the microcrystals comprise cobalt, the cobalt concentration being in the range of 1 at% to about 10 at% relative to the total transition metals in the first composition. 12.权利要求1-4任一项的粒子,其中12. The particle according to any one of claims 1-4, wherein 所述微晶包含以大约1 at%至大约60 at%的量存在的Mn,和The microcrystals contain Mn in amounts ranging from about 1 at% to about 60 at%, and 晶粒边界包含以大约1 at%至大约60 at%的量存在的Mn,其中at%分别相对于微晶或晶粒边界中的总过渡金属计。The grain boundaries contain Mn in amounts ranging from about 1 at% to about 60 at%, where at% is relative to the total transition metal in the microcrystals or grain boundaries, respectively. 13.权利要求1-4任一项的粒子,其中晶粒边界包含Ni、Co和Al。13. The particles of any one of claims 1-4, wherein the grain boundaries comprise Ni, Co, and Al. 14.权利要求1-4任一项的粒子,其中晶粒边界中的Ni浓度为相对于晶粒边界中的总过渡金属计小于90 at%。14. The particles of any one of claims 1-4, wherein the Ni concentration at the grain boundary is less than 90 at relative to the total transition metal at the grain boundary. 15.权利要求1-4任一项的粒子,其进一步包含在粒子表面上的外涂层,所述外涂层包含:15. The particle of any one of claims 1-4, further comprising an outer coating on the particle surface, said outer coating comprising: 选自Al、Zr、Y、Co、Ni、Mg和Li的一种或多种元素的氧化物;Oxides of one or more elements selected from Al, Zr, Y, Co, Ni, Mg and Li; 包含选自Al、Zr和Li的一种或多种元素的氟化物;Fluorides containing one or more elements selected from Al, Zr, and Li; 包含选自Al、Co、Ni、Mn和Li的一种或多种元素的碳酸盐;Carbonates containing one or more elements selected from Al, Co, Ni, Mn and Li; 包含选自Al、Co、Ni、Mn和Li的一种或多种元素的硫酸盐;或Sulfates containing one or more elements selected from Al, Co, Ni, Mn, and Li; or 包含选自Al和Li的一种或多种元素的磷酸盐。Phosphates containing one or more elements selected from Al and Li. 16.一种电化学活性多晶二次粒子,其包含:16. An electrochemically active polycrystalline secondary particle, comprising: 许多微晶,所述许多微晶包含由Li1+xMO2+y界定的第一组合物,其中A plurality of microcrystals, said plurality of microcrystals comprising a first composition defined by Li 1+x MO 2+y , wherein -0.1≤x≤0.3,-0.1≤x≤0.3, -0.3≤y≤0.3和-0.3≤y≤0.3 and 其中M包含大于或等于80原子%的镍;和M contains 80 atomic percent or more nickel; and 在所述许多微晶的相邻微晶之间并包含任选具有α-NaFeO2型层状结构、立方结构、尖晶石结构或其组合的第二组合物的晶粒边界,其中晶粒边界中的铝浓度大于微晶中的铝浓度,并且其中晶粒边界中的钴浓度大于微晶中的钴浓度,并且其中铝基本均匀分布在晶粒边界中。Between adjacent microcrystals of the plurality of microcrystals, there are grain boundaries of a second composition optionally having an α- NaFeO2 type layered structure, a cubic structure, a spinel structure or a combination thereof, wherein the aluminum concentration in the grain boundaries is greater than the aluminum concentration in the microcrystals, and wherein the cobalt concentration in the grain boundaries is greater than the cobalt concentration in the microcrystals, and wherein aluminum is substantially uniformly distributed in the grain boundaries. 17.权利要求16的粒子,其中晶粒边界中的钴浓度大于晶粒边界中的铝浓度。17. The particles of claim 16, wherein the cobalt concentration at the grain boundaries is greater than the aluminum concentration at the grain boundaries. 18.权利要求16的粒子,其中微晶中的钴浓度为大约0至大约17原子%,和18. The particles of claim 16, wherein the cobalt concentration in the microcrystals is from about 0 to about 17 atomic percent, and 晶粒边界中的钴浓度为大约0.5至大约32原子%,各自基于所述粒子的总原子过渡金属组合物。The cobalt concentration at the grain boundaries is from about 0.5 to about 32 atomic percent, each based on the total atomic transition metal composition of the particles. 19.权利要求16的粒子,其中M进一步包含选自Al、Mg、Co、Mn、Ca、Sr、Ba、Zn、Ti、Zr、Y、Cr、Mo、Fe、V、Si、Ga和B的一种或多种元素,所述一种或多种元素位于所述微晶的Li层、M层或两者中。19. The particles of claim 16, wherein M further comprises one or more elements selected from Al, Mg, Co, Mn, Ca, Sr, Ba, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B, said one or more elements being located in the Li layer, M layer, or both of said microcrystals. 20.权利要求16的粒子,其中M包含大于或等于90%的镍的原子%。20. The particle of claim 16, wherein M comprises 90% or more of nickel atoms. 21.一种电化学电池,其包含阴极活性材料,所述阴极活性材料包含权利要求1-20的任何一项或多项的粒子。21. An electrochemical battery comprising a cathode active material, said cathode active material comprising particles of any one or more of claims 1-20. 22.权利要求21的电化学电池,其特征在于在4.2V下的阻抗增长在45℃下对于大于100个循环小于100%。22. The electrochemical cell of claim 21, characterized in that the impedance increase at 4.2V is less than 100% for more than 100 cycles at 45°C. 23.权利要求21的电化学电池,其特征在于在4.2V下的阻抗增长在45℃下对于大于200个循环小于100%。23. The electrochemical cell of claim 21, characterized in that the impedance increase at 4.2V is less than 100% for more than 200 cycles at 45°C. 24.一种粒子,其包含:24. A particle comprising: 包含锂、镍、钴、铝和氧的总体组合物;An overall composition comprising lithium, nickel, cobalt, aluminum, and oxygen; 所述粒子包含具有第一组合物的初级微晶;The particles comprise primary microcrystals having a first composition; 在该许多微晶的相邻微晶之间并包含具有层状-NaFeO2型结构、立方结构、尖晶石结构或其组合的第二组合物的晶粒边界,Between adjacent microcrystals of these numerous microcrystals and comprising layered structures -Grain boundaries of a second composition of NaFeO2 - type structure, cubic structure, spinel structure, or combinations thereof. 其中晶粒边界中的铝相对于镍的原子分数大于微晶中的铝相对于镍的原子分数,并且其中晶粒边界中的钴相对于镍的原子分数大于微晶中的钴相对于镍的原子分数;或The atomic fraction of aluminum relative to nickel at the grain boundaries is greater than that in the crystallites, and the atomic fraction of cobalt relative to nickel at the grain boundaries is greater than that in the crystallites; or 其中晶粒边界中的铝相对于镍的原子分数大于总体组合物中的铝相对于镍的原子分数,并且其中晶粒边界中的钴相对于镍的原子分数大于总体组合物中的钴相对于镍的原子分数;或The atomic fraction of aluminum relative to nickel at the grain boundaries is greater than the atomic fraction of aluminum relative to nickel in the overall composition, and the atomic fraction of cobalt relative to nickel at the grain boundaries is greater than the atomic fraction of cobalt relative to nickel in the overall composition; or 其中晶粒边界中的铝相对于镍的原子分数大于总体组合物中的铝相对于镍的原子分数,并且其中初级微晶中的钴相对于镍的原子分数小于总体组合物中的钴相对于镍的原子分数;或The atomic fraction of aluminum relative to nickel at the grain boundaries is greater than the atomic fraction of aluminum relative to nickel in the overall composition, and the atomic fraction of cobalt relative to nickel in the primary crystallites is less than the atomic fraction of cobalt relative to nickel in the overall composition; or 它们的组合。Their combination. 25.一种形成权利要求1-4任一项的粒子的方法,其包含:25. A method for forming the particles of any one of claims 1-4, comprising: 合并锂化合物和镍化合物以形成混合物;Combining lithium compounds and nickel compounds to form a mixture; 热处理所述混合物以制造包含许多微晶和在所述许多微晶的相邻微晶之间的晶粒边界的前体,其中所述许多微晶包含含Li、Ni和O的第一组合物;The mixture is heat-treated to produce a precursor comprising a plurality of microcrystals and grain boundaries between adjacent microcrystals of the plurality of microcrystals, wherein the plurality of microcrystals comprises a first composition containing Li, Ni and O; 在包含Co和Al的工艺溶液中浸渍所述前体;The precursor is impregnated in a process solution containing Co and Al; 干燥所述前体;和Dry the precursor; and 热处理所述前体以形成粒子,其中晶粒边界中的铝浓度大于微晶中的铝浓度,并且其中晶粒边界中的钴浓度大于微晶中的钴浓度。The precursor is heat-treated to form particles, wherein the aluminum concentration at the grain boundaries is greater than the aluminum concentration in the microcrystals, and wherein the cobalt concentration at the grain boundaries is greater than the cobalt concentration in the microcrystals. 26.权利要求25的方法,其中所述液体是水性的或包含有机溶剂,任选甲醇。26. The method of claim 25, wherein the liquid is aqueous or contains an organic solvent, optionally methanol. 27.权利要求25的方法,其中所述工艺溶液包含相对于前体粒子中的总过渡金属计0.01 at%至10 at%的铝量和相对于前体粒子中的总过渡金属计0.5 at%至10 at%的钴量。27. The method of claim 25, wherein the process solution comprises an amount of aluminum of 0.01 at% to 10 at% relative to the total transition metals in the precursor particles and an amount of cobalt of 0.5 at% to 10 at% relative to the total transition metals in the precursor particles. 28.权利要求25-27任一项的方法,其中所述工艺溶液中的at% Al等于或小于所述工艺溶液中的at% Co。28. The method of any one of claims 25-27, wherein at% Al in the process solution is equal to or less than at% Co in the process solution. 29.权利要求25-27任一项的方法,其中所述许多微晶具有α-NaFeO2型层状结构、立方结构、尖晶石结构或其组合。29. The method of any one of claims 25-27, wherein the plurality of microcrystals have an α- NaFeO2 type layered structure, a cubic structure, a spinel structure, or a combination thereof. 30.权利要求25-27任一项的方法,其中所述微晶包含由Li1+xMO2+y界定的第一组合物,其中30. The method of any one of claims 25-27, wherein the microcrystals comprise a first composition defined by Li <sub>1+x</sub> MO <sub>2+y</sub> , wherein -0.1≤x≤0.3,-0.1 ≤ x ≤ 0.3, -0.3≤y≤0.3和-0.3 ≤ y ≤ 0.3 and 其中M包含大于或等于10原子%的镍。M contains 10 atomic percent or more of nickel. 31.权利要求30的方法,其中M包含大于或等于75 at%的镍的原子%。31. The method of claim 30, wherein M comprises 75 at% or more of nickel atoms. 32.权利要求30的方法,其中M进一步包含附加金属,其中所述附加金属以大约1 at%至大约90 at%的量存在;32. The method of claim 30, wherein M further comprises an additional metal, wherein the additional metal is present in an amount of about 1 at% to about 90 at%; 所述附加金属选自Mg、Sr、Co、Al、Ca、Cu、Zn、Mn、V、Ba、Zr、Ti、Cr、Fe、Mo、B和它们的任何组合。The additional metal is selected from Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B, and any combination thereof. 33.权利要求25-27任一项的方法,其中晶粒边界包含相对于晶粒边界中的总过渡金属计大约2 at%至大约99 at%的量的钴和相对于晶粒边界中的总过渡金属计大约0.5 at%至大约99 at%的量的铝。33. The method of any one of claims 25-27, wherein the grain boundary comprises cobalt in an amount of about 2 at% to about 99 at% relative to the total transition metals in the grain boundary and aluminum in an amount of about 0.5 at% to about 99 at% relative to the total transition metals in the grain boundary. 34.一种电化学电池,其包含:34. An electrochemical battery comprising: 阳极,anode, 电解质,和Electrolytes, and 阴极,所述阴极包含含有许多粒子的电化学活性阴极活性材料,所述许多粒子包含许多微晶,各微晶包含含锂、镍和氧的第一组合物;The cathode comprises an electrochemically active cathode active material containing a plurality of particles, the plurality of particles comprising a plurality of microcrystals, each microcrystal comprising a first composition containing lithium, nickel and oxygen; 在所述许多微晶的相邻微晶之间并包含具有层状-NaFeO2型结构、立方结构、尖晶石结构或其组合的第二组合物的晶粒边界;Between adjacent microcrystals of the plurality of microcrystals and comprising a layered structure -Grain boundaries of a second composition of NaFeO2 type structure, cubic structure, spinel structure or combinations thereof; 其中所述电化学活性阴极活性材料具有180 mAh/g或更大的初始放电容量;和The electrochemically active cathode material described herein has an initial discharge capacity of 180 mAh/g or greater; and 其中所述电化学电池具有在45℃下对于大于100个循环小于50%的在4.2V下的阻抗增长。The electrochemical cell described therein exhibits an impedance increase of less than 50% at 4.2V for more than 100 cycles at 45°C. 35.权利要求34的电池,其中所述电化学电池具有在45℃下对于大于200个循环小于120%的在4.2V下的阻抗增长。35. The battery of claim 34, wherein the electrochemical battery has an impedance increase of less than 120% at 4.2V for more than 200 cycles at 45°C. 36.权利要求34的电池,其特征在于在50%充电状态下的阻抗增长为在45℃下对于大于200个循环小于50%。36. The battery of claim 34, characterized in that the impedance increase at 50% charge is less than 50% for more than 200 cycles at 45°C. 37.权利要求34的电池,其中各微晶包含锂、镍、钴和氧。37. The battery of claim 34, wherein each microcrystal comprises lithium, nickel, cobalt and oxygen. 38.权利要求37的电池,其中各微晶进一步包含Al。38. The battery of claim 37, wherein each microcrystal further comprises Al. 39.权利要求37的电池,其中各微晶进一步包含Mn。39. The battery of claim 37, wherein each microcrystal further comprises Mn. 40.权利要求37的电池,其中各微晶进一步包含Mg。40. The battery of claim 37, wherein each microcrystal further comprises Mg. 41.权利要求34的电池,其中第一组合物和第二组合物具有相同元素。41. The battery of claim 34, wherein the first composition and the second composition have the same elements. 42.权利要求34-41任一项的电池,其中第一组合物由Li1+xMO2+y界定,其中42. The battery of any one of claims 34-41, wherein the first composition is defined by Li 1+x MO 2+y , wherein -0.95≤x≤0.3,-0.95≤x≤0.3, -0.3≤y≤0.3和-0.3≤y≤0.3 and 其中M包含大于或等于80原子%的镍。M contains 80 atomic percent or more of nickel. 43.权利要求42的电池,其中M进一步包含选自Mg、Sr、Co、Al、Ca、Cu、Zn、Mn、V、Ba、Zr、Ti、Nb、Ta、Cr、Fe、Mo、W、Hf和B的一种或多种元素,所述一种或多种元素位于所述微晶的Li层、M层或两者中。43. The battery of claim 42, wherein M further comprises one or more elements selected from Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Nb, Ta, Cr, Fe, Mo, W, Hf and B, said one or more elements being located in the Li layer, M layer or both of the microcrystals. 44.权利要求42的电池,其中M包含大于或等于90%的镍的原子%。44. The battery of claim 42, wherein M comprises 90% or more nickel atoms. 45.权利要求34-41任一项的电池,其中所述微晶包含钴,钴浓度在相对于第一组合物中的总过渡金属计1 at%至大约50 at%的范围内。45. The battery of any one of claims 34-41, wherein the microcrystals comprise cobalt, the cobalt concentration being in the range of 1 at% to about 50 at% relative to the total transition metals in the first composition. 46.权利要求34-41任一项的电池,其中所述微晶包含钴,钴浓度在相对于微晶中的总过渡金属计1 at%至大约15 at%的范围内。46. The battery of any one of claims 34-41, wherein the microcrystals comprise cobalt, the cobalt concentration being in the range of 1 at% to about 15 at% relative to the total transition metals in the microcrystals. 47.权利要求34-41任一项的电池,其中所述微晶包含Co和Mg。47. The battery of any one of claims 34-41, wherein the microcrystals comprise Co and Mg. 48.权利要求34-41任一项的电池,其中第二组合物包含Al。48. The battery of any one of claims 34-41, wherein the second composition comprises Al. 49.权利要求34-41任一项的电池,其中第一组合物不包括Al。49. The battery of any one of claims 34-41, wherein the first composition does not include Al. 50.权利要求34-41任一项的电池,其中第二组合物中的Al在所述许多粒子中基本均匀分布。50. The battery of any one of claims 34-41, wherein the Al in the second composition is substantially uniformly distributed among the plurality of particles. 51.权利要求34-41任一项的电池,其中Al以相对于第一组合物中的总过渡金属计小于4原子%存在。51. The battery of any one of claims 34-41, wherein Al is present in a concentration of less than 4 atomic percent relative to the total transition metals in the first composition.
CN202610182632.7A 2019-01-17 2019-10-23 Polycrystalline metal oxide with enriched grain boundaries Pending CN122000331A (en)

Applications Claiming Priority (8)

Application Number Priority Date Filing Date Title
US201916250762A 2019-01-17 2019-01-17
US16/250,622 US10950857B2 (en) 2019-01-17 2019-01-17 Polycrystalline metal oxides with enriched grain boundaries
US16/250,615 2019-01-17
US16/250,762 2019-01-17
US16/250,622 2019-01-17
US16/250,615 US10501335B1 (en) 2019-01-17 2019-01-17 Polycrystalline metal oxides with enriched grain boundaries
PCT/US2019/057630 WO2020149910A1 (en) 2019-01-17 2019-10-23 Polycrystalline metal oxides with enriched grain boundaries
CN201980094065.8A CN113678285A (en) 2019-01-17 2019-10-23 Polycrystalline metal oxides with enriched grain boundaries

Related Parent Applications (1)

Application Number Title Priority Date Filing Date
CN201980094065.8A Division CN113678285A (en) 2019-01-17 2019-10-23 Polycrystalline metal oxides with enriched grain boundaries

Publications (1)

Publication Number Publication Date
CN122000331A true CN122000331A (en) 2026-05-08

Family

ID=71613350

Family Applications (2)

Application Number Title Priority Date Filing Date
CN202610182632.7A Pending CN122000331A (en) 2019-01-17 2019-10-23 Polycrystalline metal oxide with enriched grain boundaries
CN201980094065.8A Pending CN113678285A (en) 2019-01-17 2019-10-23 Polycrystalline metal oxides with enriched grain boundaries

Family Applications After (1)

Application Number Title Priority Date Filing Date
CN201980094065.8A Pending CN113678285A (en) 2019-01-17 2019-10-23 Polycrystalline metal oxides with enriched grain boundaries

Country Status (6)

Country Link
EP (1) EP3912209A4 (en)
JP (2) JP7629403B2 (en)
KR (2) KR20210105440A (en)
CN (2) CN122000331A (en)
CA (1) CA3126058A1 (en)
WO (1) WO2020149910A1 (en)

Families Citing this family (5)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN114051487B (en) * 2019-07-03 2024-03-22 尤米科尔公司 Lithium nickel manganese cobalt composite oxide as positive electrode active material for rechargeable lithium ion battery
JP7652891B2 (en) * 2020-11-10 2025-03-27 エルジー エナジー ソリューション リミテッド Positive electrode active material for lithium secondary battery, method for producing same and lithium secondary battery including same
KR20220087953A (en) * 2020-12-18 2022-06-27 주식회사 포스코 Positive active material for rechargeable lithium battery, method for preparing same, and rechargeable lithium battery including same
KR102867394B1 (en) 2021-12-21 2025-10-01 포스코홀딩스 주식회사 Positive active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same
KR20250142148A (en) * 2024-03-21 2025-09-30 주식회사 엘지에너지솔루션 Positive electrode active material, method for preparing the same, positive electrode and lithium secondary battery comprising the same

Family Cites Families (8)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2010211925A (en) 2009-03-06 2010-09-24 Panasonic Corp Positive electrode active material for nonaqueous electrolyte secondary battery, method of manufacturing the same, and nonaqueous electrolyte secondary battery
KR101297175B1 (en) 2011-03-10 2013-08-21 삼성에스디아이 주식회사 Positive active material for rechargeable lithium battery, method of manufacturing the same and rechargeable lithium battery using the same
PL2744754T3 (en) 2011-08-16 2017-04-28 Tiax Llc Polycrystalline metal oxide, methods of manufacture thereof, and articles comprising the same
JP5971109B2 (en) * 2011-12-20 2016-08-17 住友金属鉱山株式会社 Nickel composite hydroxide and production method thereof, positive electrode active material for non-aqueous electrolyte secondary battery, production method thereof, and non-aqueous electrolyte secondary battery
JP2015213038A (en) * 2014-05-07 2015-11-26 日立マクセル株式会社 Positive electrode material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
KR20230017921A (en) * 2016-04-27 2023-02-06 캠엑스 파워 엘엘씨 Polycrystalline layered metal oxides comprising nano-crystals
KR20190003110A (en) * 2017-06-30 2019-01-09 삼성전자주식회사 Composite cathode active material, Cathode and Lithium battery containing composite cathode active material and Preparation method thereof
US11081693B2 (en) 2017-08-30 2021-08-03 Samsung Electronics Co., Ltd. Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material

Also Published As

Publication number Publication date
EP3912209A4 (en) 2022-11-30
JP2025026975A (en) 2025-02-26
JP2022522999A (en) 2022-04-21
EP3912209A1 (en) 2021-11-24
CA3126058A1 (en) 2020-07-23
JP7629403B2 (en) 2025-02-13
WO2020149910A1 (en) 2020-07-23
JP7857680B2 (en) 2026-05-13
CN113678285A (en) 2021-11-19
KR20210105440A (en) 2021-08-26
KR20260008192A (en) 2026-01-15

Similar Documents

Publication Publication Date Title
US10843936B2 (en) Polycrystalline metal oxides with enriched grain boundaries
US11682762B2 (en) Nanocrystals of polycrystalline layered lithium nickel metal oxides
EP3141528B1 (en) Polycrystalline metal oxide, methods of manufacture thereof, and articles comprising the same
JP7857680B2 (en) Polycrystalline metal oxides with concentrated grain boundaries
US10950857B2 (en) Polycrystalline metal oxides with enriched grain boundaries
US20230197947A1 (en) Stable cathode materials
CN113614958A (en) Stabilized cathode materials
WO2020150084A1 (en) Stable cathode materials
KR20260026085A (en) High-energy, long-cycle life cathode materials and batteries using them

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination